Inorganic solid electrolyte-containing composition, sheet for all-solid-state secondary battery, all-solid-state secondary battery, and method for producing sheet for all-solid-state secondary battery, and method for producing all-solid-state secondary battery
By using a composition containing an inorganic solid electrolyte, a polymer binder and specific functional groups in an all-solid secondary battery, the problem of limited interface contact state between solid particles is solved, and an all-solid secondary battery with low resistance and excellent cycle characteristics is achieved.
Patent Information
- Application Number
- CN202380059923.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-30
- Filing Date
- 2023-09-25
- Publication Date
- 2025-03-28
AI Technical Summary
In an all-solid-state secondary battery, the interface contact state between solid particles is limited, resulting in an increase in interface resistance and affecting battery performance.
A composition containing an inorganic solid electrolyte, a polymer binder and a compound of specific functional groups is used to improve the dispersion stability and operability of solid particles through synergistic action to form a structural layer with low resistance.
It achieves a firm close bond between solid particles, reduces the resistance of the battery, and improves the circulation characteristics and overall performance of the battery.
Smart Images

Figure CN119731747A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an inorganic solid electrolyte composition, a sheet material for an all-solid-state secondary battery and an all-solid-state secondary battery, and a method for manufacturing the sheet material for an all-solid-state secondary battery and the all-solid-state secondary battery. Background Art
[0002] In an all-solid-state secondary battery, the negative electrode, electrolyte and positive electrode are all composed of solids, which can greatly improve the safety and reliability of batteries using organic electrolytes. And it can also extend the life. In addition, the all-solid-state secondary battery can be set to a structure in which the electrodes and electrolytes are directly arranged and configured in series. Therefore, compared with secondary batteries using organic electrolytes, it can be highly energy-dense, and is expected to be applied to electric vehicles or large batteries.
[0003] In all-solid-state secondary batteries, as materials forming structural layers (solid electrolyte layer, negative electrode active material layer, positive electrode active material layer, etc.), inorganic solid electrolytes, active materials, conductive additives, etc. can be used. In recent years, the inorganic solid electrolytes, especially oxide-based inorganic solid electrolytes and sulfide-based inorganic solid electrolytes, have been expected as electrolyte materials with high ionic conductivity close to that of organic electrolytes.
[0004] Considering the improvement of productivity, etc., the structural layer formed using this inorganic solid electrolyte is usually formed using a material containing an inorganic solid electrolyte (structural layer forming material). At this time, it is known that there are technologies such as dispersants containing inorganic solid electrolytes for the purpose of improving the dispersibility of the inorganic solid electrolyte in the structural layer forming material and battery performance. For example, in Patent Document 1, it is recorded that "a positive electrode material contains a positive electrode active material, an inorganic solid electrolyte having ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, a conductive additive, and a dispersant containing a compound having at least one specific functional group".
[0005] The structural layer of the all-solid-state secondary battery is formed by solid particles (inorganic solid electrolytes, active materials, conductive additives, etc.), so the interface contact state between the solid particles and the interface contact state between the solid particles and the collector are usually limited. As a result, the interface resistance is easy to increase, and the solid particles cannot be tightly bonded to each other through a strong adhesion. The increase in the interface resistance not only causes the increase in the battery resistance of the all-solid-state secondary battery (the decrease in the conductivity of ions or electrons), but also causes the decrease in the cycle characteristics. Moreover, the adhesion between the solid particles is not sufficient, which leads to a further decrease in the cycle characteristics. The increase in resistance, which is the main reason for the decline in battery performance, is not only related to the interface contact state between the solid particles, but also to the uneven presence (configuration) of the solid particles in the structural layer, and the surface flatness of the structural layer is also the main reason. Therefore, when the structural layer is formed by a structural layer forming material, the following properties are required for the structural layer forming material: the property of stably maintaining the excellent dispersibility of the solid particles just prepared (dispersion stability); and the property of having moderate viscosity, high fluidity, and being able to form a good coating (operability).
[0006] In order to improve the dispersibility and adhesion of solid particles, it is effective to use a binder such as a polymer binder in the structural layer forming material. However, the electronic and ionic conductivity of the binder is generally low, so if the binder is used at the same time, the resistance increases, and it becomes difficult to take into account both the dispersion stability of the structural layer forming material and the suppression of the resistance increase of the formed structural layer.
[0007] In this case, Patent Document 1 does not conduct research from the above viewpoint, but various studies have been conducted on structural layer forming materials containing inorganic solid electrolytes and polymer binders. For example, Patent Document 2 records "an inorganic solid electrolyte composition for an all-solid-state secondary battery, which contains an inorganic solid electrolyte having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, a polymer binder, a compound containing a metal element, and a dispersion medium, wherein the compound containing a metal element is a compound that can supply the metal element constituting the molecule as an ion to a polymer forming the polymer binder, the polymer binder is dissolved in the dispersion medium, and the compound containing the metal element exists in a solid state." According to Patent Document 2, the following is recorded: The inorganic solid electrolyte composition formed by using a compound containing a metal element that performs the above-mentioned function on the polymer binder shows excellent dispersion stability and operability, but can achieve a low-resistance structural layer.
[0008] Previous technical literature
[0009] Patent Literature
[0010] Patent Document 1: International Publication No. 2016 / 194759
[0011] Patent Document 2: International Publication No. 2021 / 157278 Summary of the invention
[0012] Technical issues to be solved by the invention
[0013] The subject of the present invention is to provide an inorganic solid electrolyte composition, which shows excellent dispersion stability and operability, wherein, by being used as a structural layer forming material for an all-solid-state secondary battery, an all-solid-state secondary battery with low resistance and excellent cycle characteristics can be realized. In addition, the subject of the present invention is to provide a sheet material for an all-solid-state secondary battery and an all-solid-state secondary battery using the inorganic solid electrolyte composition, as well as a method for manufacturing the sheet material for an all-solid-state secondary battery and the all-solid-state secondary battery.
[0014] Means for solving technical problems
[0015] The present inventors have conducted various studies on inorganic solid electrolyte compositions containing inorganic solid electrolytes and polymer binders, and found that the results are as follows: although having specific functional groups and molecular weights, the compound (A) dissolved in the dispersion medium is used simultaneously with the inorganic solid electrolyte and the polymer binder having a specific mass average molecular weight, thereby enabling the polymer binder and the compound (A) to synergize to achieve excellent dispersion stability and operability. In addition, it is found that by using the inorganic solid electrolyte composition as a structural layer forming material, it is possible to realize a sheet for an all-solid-state secondary battery having a low-resistance structural layer in which solid particles are firmly bonded (bonded), and an all-solid-state secondary battery having low resistance and excellent cycle characteristics.
[0016] The present invention was completed by conducting further studies based on these findings.
[0017] That is, the above-mentioned problems were solved by the following means.
[0018] <1> An inorganic solid electrolyte composition comprising an inorganic solid electrolyte (SE) having ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, a polymer binder (B), a compound (A) and a dispersion medium (D), and satisfying the following conditions (1) to (4).
[0019] Condition (1) The mass average molecular weight of the polymer constituting the polymer binder (B) is 2,000 or more
[0020] Condition (2) Compound (A) has at least one functional group selected from the following functional group group (a):
[0021] Condition (3) The molecular weight of compound (A) is less than 2,000
[0022] Condition (4) Compound (A) is dissolved in dispersion medium (D)
[0023] [Functional group (a)]
[0024] Hydroxyl, amino, carboxyl, sulfonic acid, phosphoric acid, phosphonic acid, cyano, thiol, sulfinyl
[0025] <2> The inorganic solid electrolyte-containing composition according to <1>, wherein
[0026] The content of the compound (A) is 10 ppm or more relative to 100% by mass of the solid content of the inorganic solid electrolyte composition and 2.0×10 3 Below ppm.
[0027] <3> The inorganic solid electrolyte composition according to <1> or <2>, wherein
[0028] The polymer binder (B) is dissolved in the dispersion medium (D).
[0029] <4> The inorganic solid electrolyte-containing composition according to any one of <1> to <3>, wherein
[0030] The molecular weight of compound (A) is less than 600.
[0031] <5> The inorganic solid electrolyte-containing composition according to any one of <1> to <4>, wherein
[0032] The compound (A) satisfies the following condition (5).
[0033] Condition (5) The residue after removing the functional group from the compound (A) has the same chemical structure as the terminal group of the polymer constituting the polymer binder (B) bonded to the heteroatom linking group
[0034] <6> The inorganic solid electrolyte-containing composition according to any one of <1> to <5>, wherein
[0035] The polymer binder (B) is a (meth)acrylic polymer.
[0036] <7> The inorganic solid electrolyte-containing composition according to any one of <1> to <6>, comprising an active material (AC).
[0037] <8> A sheet for an all-solid-state secondary battery, comprising a layer formed from the inorganic solid electrolyte composition according to any one of <1> to <7>.
[0038] <9> An all-solid-state secondary battery comprising, in order, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer, wherein:
[0039] At least one of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer is a layer formed of the inorganic solid electrolyte composition described in any one of <1> to <7>.
[0040] <10> A method for producing a sheet for an all-solid-state secondary battery, comprising forming a film of the inorganic solid electrolyte-containing composition according to any one of <1> to <7> above.
[0041] <11> A method for manufacturing an all-solid-state secondary battery, comprising manufacturing the all-solid-state secondary battery by the manufacturing method described in <10> above.
[0042] Effects of the Invention
[0043] The present invention can provide a kind of inorganic solid electrolyte composition, which shows excellent dispersion stability and operability, and can realize low resistance and excellent cycle characteristics of all-solid-state secondary battery. In addition, the present invention can provide a kind of all-solid-state secondary battery sheet and all-solid-state secondary battery with a layer formed by the excellent inorganic solid electrolyte composition. In addition, the present invention can provide a kind of all-solid-state secondary battery sheet and all-solid-state secondary battery manufacturing method using the inorganic solid electrolyte composition.
[0044] The above-mentioned features, other features and advantages of the present invention will become more apparent from the following description with reference to the accompanying drawings as appropriate. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 It is a longitudinal sectional view schematically showing an all-solid-state secondary battery according to a preferred embodiment of the present invention.
[0046] Figure 2 It is a longitudinal cross-sectional view schematically showing a button-type all-solid-state secondary battery produced in the example. DETAILED DESCRIPTION
[0047] In the present invention, when a numerical range is shown and the content, physical properties, etc. of a component are described, when the upper limit and lower limit of the numerical range are described separately, any upper limit and lower limit can be appropriately combined to be set to a specific numerical range. On the other hand, when a plurality of numerical ranges represented by "to" are set for description, the upper limit and lower limit forming the numerical range are not limited to the specific combination recorded before and after "to" as a specific numerical range, and can be set to a numerical range formed by appropriately combining the upper limit and lower limit of each numerical range. In addition, in the present invention, the numerical range represented by "to" represents a range including the numerical values recorded before and after "to" as the lower limit and upper limit.
[0048] In the present invention, the expression of a compound (for example, when the compound is added to the end) is used to include not only the compound itself but also its salt and ion. Furthermore, it means that a derivative obtained by changing a part such as introducing a substituent is included within the range that does not impair the effect of the present invention.
[0049] In the present invention, (meth)acrylic acid means one or both of acrylic acid and methacrylic acid. The same applies to (meth)acrylate.
[0050] In the present invention, the fact that a substituted or unsubstituted substituent, a linking group, etc. (hereinafter referred to as a substituent, etc.) is not clearly described indicates that the group may have an appropriate substituent. Therefore, in the present invention, when simply described as a YYY group, the YYY group includes not only a mode without a substituent, but also a mode with a substituent. This also has the same meaning for compounds that are not clearly indicated to be substituted or unsubstituted. As a preferred substituent, for example, a group selected from the substituent Z described later can be cited.
[0051] In the present invention, when there are multiple substituents etc. represented by specific symbols, or when multiple substituents etc. are specified simultaneously or alternatively, it means that each substituent etc. may be the same or different from each other. Furthermore, it means that even if there is no special description, when multiple substituents etc. are adjacent, they may be linked or fused to each other to form a ring.
[0052] In the present invention, "ppm" indicating a content or the like is based on mass and means "mass ppm" unless otherwise specified.
[0053] In the present invention, polymer means a polymer, which has the same meaning as a so-called high molecular compound. In addition, polymer binder (also referred to as binder) means a binder composed of a polymer, including the polymer itself and a binder composed (formed) of a polymer.
[0054] In the present invention, the main chain of a polymer or a polymer chain refers to a linear molecular chain constituting a polymer or a polymer chain, and all other molecular chains can be regarded as branch chains or side groups relative to the main chain. Although it also depends on the mass average molecular weight of the branched chain regarded as a branched chain or a side group, typically, the longest chain in the molecular chain constituting a polymer or a polymer chain becomes the main chain. Among them, the terminal group possessed by the end of the polymer or the polymer chain is not included in the main chain. In addition, the side chain of a polymer refers to a branched chain other than the main chain, including a short chain and a long chain.
[0055] [Inorganic solid electrolyte composition]
[0056] The inorganic solid electrolyte composition of the present invention contains an inorganic solid electrolyte (SE) having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, a polymer binder (B), a compound (A) and a dispersion medium (D), and satisfies the following conditions (1) to (4). The inorganic solid electrolyte composition exhibits excellent dispersion stability and operability, and an all-solid-state secondary battery having a structural layer formed by the inorganic solid electrolyte composition has low resistance and excellent cycle characteristics.
[0057] Although the detailed reason is not clear, it is considered as follows.
[0058] In the inorganic solid electrolyte composition, the polymer binder (B) is composed of a polymer having a specific molecular weight (condition (1)), so the molecular chain is easily unfolded in the dispersion medium (D), and the adsorbed solid particles can be mutually repelled to inhibit (re)aggregation or precipitation, thereby improving dispersibility. In addition, it is believed that since the compound (A) has a specific functional group (condition (2)), it is adsorbed on solid particles such as inorganic solid electrolytes, and because it has a specific molecular weight, it is dissolved in the dispersion medium (D) (conditions (3) and conditions (4)), so the interaction with the polymer binder (B) is expressed by the basic skeleton (residues excluding the functional groups) other than the functional groups. As a result, it is speculated that the compound (A) enhances the dispersibility improvement effect of the polymer binder (D) on the solid particles in the dispersion medium (D). The inorganic solid electrolyte composition of the present invention suppresses the (re)aggregation and precipitation of solid particles just after preparation and over time, and shows excellent initial dispersibility and dispersion stability, while also showing moderate fluidity.
[0059] Moreover, the inorganic solid electrolyte composition showing the above-mentioned effect can maintain direct contact between solid particles (not via contact of adhesive) during film making, without greatly damaging the firm closeness between solid particles. In addition, the following structural layer can be formed: moderate flow (leveling) to suppress the segregation of solid particles, and suppress the generation of surface roughness of concave and convex caused by insufficient flow or excessive flow, and surface roughness caused by blocking the discharge portion during coating. Therefore, it is believed that the inorganic solid electrolyte composition of the present invention can form the following structural layer: although the solid particles are firmly close or bonded to each other, the contact between the solid particles that suppress segregation is maintained, and sufficient conductive paths (ionic conductive paths and electronic conductive paths) throughout the entire structural layer are constructed to reduce interface resistance. This structural layer is not easy to generate overcurrent during the charge and discharge of the all-solid-state secondary battery, and can also prevent the degradation of solid particles, and can suppress the decline of battery characteristics caused by the passage of time of the all-solid-state secondary battery.
[0060] When the inorganic solid electrolyte composition of the present invention showing the above-mentioned effects is used as a structural layer forming material, an all-solid-state secondary battery sheet having a low-resistance structural layer in which solid particles are firmly bonded and an all-solid-state secondary battery showing low resistance and excellent cycle characteristics can be produced.
[0061] It is believed that in the inorganic solid electrolyte composition of the present invention, the polymer binder (B) is also adsorbed on the inorganic solid electrolyte (SE) and the active material (AC), and is between the solid particles, thereby showing the function of dispersing the solid particles in the dispersion medium (D). Here, the adsorption of each solid particle by the polymer binder (B) is not particularly limited, and includes not only physical adsorption, but also chemical adsorption (adsorption generated by the formation of chemical bonds, adsorption generated by electron donation, etc.). In addition, it is believed that the compound (A) enhances the adsorption between the polymer binder (B) and the solid particles. The compound (A) can exist alone in the inorganic solid electrolyte composition, but preferably interacts with the polymer binder (B) or is adsorbed on the solid particles.
[0062] On the other hand, polymer binder (B) functions as a binder for bonding solid particles in the structural layer. And, sometimes, it functions as a binder for bonding current collector and solid particles. It is believed that compound (A) also enhances the adsorption between polymer binder (B) and solid particles in the structural layer, and can exist alone, but preferably interacts with polymer binder (B) or is adsorbed on solid particles.
[0063] It is believed that in the inorganic solid electrolyte composition and structural layer of the present invention, the compound (A) interacts with the polymer binder (B) and is adsorbed on the solid particles, thereby showing the function of enhancing the adsorption of the polymer binder (B) on the solid particles. Here, the adsorption of the compound (A) on the polymer binder (B) is not particularly limited, including physical adsorption, chemical adsorption (adsorption generated by intermolecular forces, adsorption generated by electron donation, etc.). In addition, the adsorption of the compound (A) on the solid particles is not particularly limited, including physical adsorption, chemical adsorption (adsorption generated by the formation of chemical bonds, adsorption generated by electron donation, etc.).
[0064] As described above, the inorganic solid electrolyte-containing composition of the present invention satisfies the following conditions (1) to (4). Each condition can also be said to be a condition that the compound (A) satisfies with respect to the inorganic solid electrolyte (SE), the polymer binder (B) and the dispersion medium (D).
[0065] Each condition is described below.
[0066] Condition (1): The mass average molecular weight of the polymer constituting the polymer binder (B) is 2,000 or more
[0067] In the inorganic solid electrolyte composition of the present invention, if condition (1) is combined with other conditions described later, the molecular chain (molecular structure) of the polymer (b) constituting the polymer binder (B) is expanded in the dispersion medium (D), thereby further suppressing the aggregation of solid particles and further improving the dispersion characteristics (initial dispersibility and dispersion stability). From the perspective of being able to further improve the dispersion characteristics, the mass average molecular weight of the polymer (b) is preferably 50,000 or more, more preferably 100,000 or more, and more preferably 200,000 or more. On the other hand, from the perspective of being able to suppress excessive coating of the surface of solid particles and construct a sufficient conductive path, the mass average molecular weight is preferably 1,000,000 or less, more preferably 800,000 or less, and more preferably 600,000 or less.
[0068] The mass average molecular weight of the polymer (b) can be appropriately adjusted by changing the type and content of the polymerization initiator and the like, the polymerization time, the polymerization temperature, and the like.
[0069] - Determination of Molecular Weight -
[0070] In the present invention, unless otherwise specified, the molecular weight of a polymer, a polymer chain, a polymer chain, and a macromonomer refers to the mass average molecular weight or number average molecular weight converted to standard polystyrene obtained by gel permeation chromatography (GPC). As its determination method, basically, a method set to the following determination condition 1 or determination condition 2 (preferred) can be cited. Among them, a suitable eluent can be appropriately selected according to the type of polymer, etc. for use.
[0071] (Measurement Condition 1)
[0072] Column: Two TOSOH TSKgel Super AWM-H (product name, manufactured by Tosoh Corporation) connected
[0073] Carrier: 10mMLiBr / N-methylpyrrolidone
[0074] Measuring temperature: 40℃
[0075] Carrier flow rate: 1.0ml / min
[0076] Sample concentration: 0.1 mass%
[0077] Detector: RI (refractive index) detector
[0078] (Measurement Condition 2)
[0079] Column: A column obtained by connecting TOSOH TSKgel Super HZM-H, TOSOH TSKgel Super HZ4000, and TOSOH TSKgel Super HZ2000 (all product names, manufactured by Tosoh Corporation) was used.
[0080] Charge carrier: Tetrahydrofuran
[0081] Measuring temperature: 40℃
[0082] Carrier flow rate: 1.0ml / min
[0083] Sample concentration: 0.1 mass%
[0084] Detector: RI (refractive index) detector
[0085] Condition (2): Compound (A) has at least one functional group selected from the following functional group group (a) [functional group (a)] hydroxyl, amino, carboxyl, sulfonic acid, phosphoric acid, phosphonic acid, cyano, thiol, sulfinyl
[0086] It is believed that in the inorganic solid electrolyte composition of the present invention, if other conditions are combined with condition (2), the adsorption force of compound (A) on solid particles is improved, and the adsorption between the polymer binder (B) and the solid particles is enhanced, thereby further improving the dispersibility improvement function of the polymer binder (B) in the dispersion medium (D).
[0087] The details of condition (2) will be described later.
[0088] Condition (3): The molecular weight of compound (A) is less than 2,000
[0089] It is believed that in the inorganic solid electrolyte-containing composition of the present invention, if other conditions are combined with condition (3), the interaction with the polymer binder (B) is manifested, thereby enhancing the dispersibility improvement function of the polymer binder (B) in the dispersion medium (D). From the perspective of further enhancing the dispersibility improvement function of the polymer binder (B), the molecular weight of the compound (A) is preferably 1,000 or less, more preferably less than 600, further preferably less than 500, and particularly preferably 300 or less. The lower limit of the molecular weight of the compound (A) is not particularly limited and can be appropriately set, for example, it can be set to 100 or more, preferably 150 or more.
[0090] When compound (A) is a polymer, its molecular weight means the mass average molecular weight measured in the same manner as the polymer binder (B). The mass average molecular weight in this case can be appropriately adjusted by changing the type, content, polymerization time, polymerization temperature, etc. of the polymerization initiator, etc.
[0091] Condition (4): Compound (A) is dissolved in dispersion medium (D)
[0092] The compound (A) contained in the inorganic solid electrolyte composition of the present invention shows the property of being dissolved in the dispersion medium (D) (solubility). The compound (A) in the inorganic solid electrolyte composition also depends on the content of the dispersion medium (D), but usually exists in the inorganic solid electrolyte composition in a state dissolved in the dispersion medium (D).
[0093] In the inorganic solid electrolyte-containing composition of the present invention, when condition (4) is combined with conditions (1) to (3), the polymer binder (B) is easily adsorbed in the dispersion medium (D), thereby enhancing the dispersibility improvement function of the polymer binder (B).
[0094] In the present invention, the solubility of the compound (A) in the dispersion medium (D) can be appropriately imparted by the type of compound (A), the molecular weight of the compound (A), the type of functional group selected from the functional group group (a) described later or its content, and the combination with the dispersion medium (D).
[0095] In the present invention, the compound (A) is dissolved in the dispersion medium (D) means that the compound (A) is dissolved in the dispersion medium (D) in the inorganic solid electrolyte composition, for example, it means that the solubility in the solubility measurement is 10% by mass or more. On the contrary, the compound (A) is not dissolved in the dispersion medium (D) (insoluble) means that the solubility in the solubility measurement is less than 10% by mass.
[0096] The method for determining the solubility is as follows. That is, accurately weigh about 0.1 g of the compound (A), and set the accurately weighed mass as W0. Next, place the compound (A) and 10 g of a dispersion medium having the same composition as the dispersion medium (D) contained in the inorganic solid electrolyte composition in a container, and mix them at a temperature of 25°C and a rotation speed of 100 rpm for 48 hours using a mixing rotor (model VMR-5, manufactured by AS ONE Corporation.). Thereafter, filter out the insoluble matter from the solution, vacuum dry the obtained solid at 120°C for 3 hours, and accurately weigh the mass W1 of the insoluble matter. Moreover, the solubility (%) in the dispersion medium (D) is calculated according to the following formula, and the obtained value is used as the solubility of the compound (A) in the dispersion medium (D).
[0097] Solubility (%) = (W0-W1) / W0×100
[0098] The inorganic solid electrolyte-containing composition of the present invention is preferably a slurry in which the inorganic solid electrolyte (SE) is dispersed in a dispersion medium (D).
[0099] The inorganic solid electrolyte composition of the present invention is preferably a non-aqueous composition. In the present invention, the non-aqueous composition, in addition to the mode of not containing water, also includes a mode in which the water content (also referred to as water content) is preferably 500ppm or less. In the non-aqueous composition, the water content is more preferably 200ppm or less, further preferably 100ppm or less, and particularly preferably 50ppm or less. If the inorganic solid electrolyte composition is a non-aqueous composition, the degradation of the inorganic solid electrolyte can be suppressed. The water content represents the amount of water contained in the inorganic solid electrolyte composition (relative to the mass ratio of the inorganic solid electrolyte composition), specifically, it is set to be filtered using a 0.02μm membrane filter and the value measured using Karl Fischer titration.
[0100] The inorganic solid electrolyte composition of the present invention exhibits the above-mentioned excellent properties, and therefore can be preferably used as a material for forming a sheet for an all-solid-state secondary battery and a structural layer of an all-solid-state secondary battery. In the structural layer, it can be preferably used as a material for forming a solid electrolyte layer and an active material layer, especially a positive electrode active material layer, and a negative electrode active material layer containing a negative electrode active material that expands and contracts greatly due to charge and discharge.
[0101] The inorganic solid electrolyte-containing composition of the present invention includes an embodiment that contains an active material and the like in addition to the inorganic solid electrolyte (a composition of this embodiment is referred to as an electrode composition).
[0102] Hereinafter, components contained in the inorganic solid electrolyte-containing composition of the present invention and components that may be contained are described.
[0103] <Inorganic solid electrolyte>
[0104] The inorganic solid electrolyte-containing composition of the present invention contains an inorganic solid electrolyte.
[0105] In the present invention, an inorganic solid electrolyte refers to an inorganic solid electrolyte, and a solid electrolyte refers to a solid electrolyte in which ions can be moved. As the main ion conductive material, it does not contain organic matter, so it is clearly distinguished from an organic solid electrolyte (a polymer electrolyte represented by polyethylene oxide (PEO), etc., an organic electrolyte salt represented by lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), etc.). In addition, an inorganic solid electrolyte is solid in a stable state, so it is usually not dissociated or freed into cations and anions. At this point, it is also clearly distinguished from an inorganic electrolyte salt (LiPF6, LiBF4, lithium bis(fluorosulfonyl)imide (LiFSI), LiCl, etc.) that is dissociated or freed into cations and anions in an electrolyte or in a polymer. As long as the inorganic solid electrolyte has the conductivity of the ions of a metal belonging to Group 1 or Group 2 of the periodic table, it is not particularly limited and usually does not have electronic conductivity.
[0106] The above-mentioned inorganic solid electrolyte can be appropriately selected from solid electrolyte materials commonly used in all-solid-state secondary batteries. For example, as inorganic solid electrolytes, (i) sulfide-based inorganic solid electrolytes, (ii) oxide-based inorganic solid electrolytes, (iii) halide-based inorganic solid electrolytes, and (iv) hydride-based inorganic solid electrolytes can be cited. From the viewpoint of being able to form a better interface between the active material and the inorganic solid electrolyte, sulfide-based inorganic solid electrolytes are preferred.
[0107] When the all-solid-state secondary battery of the present invention is a lithium-ion battery, the inorganic solid electrolyte preferably has ionic conductivity of lithium ions.
[0108] (i) Sulfide-based inorganic solid electrolytes
[0109] The sulfide-based inorganic solid electrolyte is preferably a compound containing sulfur atoms and having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table and having electronic insulation. The sulfide-based inorganic solid electrolyte preferably contains at least Li, S, and P as elements and has lithium ion conductivity, but may also appropriately contain other elements other than Li, S, and P.
[0110] Examples of the sulfide-based inorganic solid electrolyte include lithium ion conductive inorganic solid electrolytes satisfying a composition represented by the following formula (S1).
[0111] L a1 M b1 P c1 S d1 A e1 (S1)
[0112] In formula (S1), L represents an element selected from Li, Na and K, preferably Li. M represents an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al and Ge. A represents an element selected from I, Br, Cl and F. a1 to e1 represent the composition ratio of each element, and a1:b1:c1:d1:e1 satisfies 1 to 12:0 to 5:1:2 to 12:0 to 10. a1 is preferably 1 to 9, and more preferably 1.5 to 7.5. b1 is preferably 0 to 3, and more preferably 0 to 1. d1 is preferably 2.5 to 10, and more preferably 3.0 to 8.5. e1 is preferably 0 to 5, and more preferably 0 to 3.
[0113] As described below, the composition ratio of each element can be controlled by adjusting the blending amounts of the raw material compounds when producing the sulfide-based inorganic solid electrolyte.
[0114] The sulfide-based inorganic solid electrolyte may be amorphous (glass), crystallized (glass ceramic), or only partially crystallized. For example, Li-PS glass containing Li, P, and S or Li-PS glass ceramic containing Li, P, and S may be used.
[0115] Sulfide-based inorganic solid electrolytes can be manufactured by reacting at least two or more raw materials including lithium sulfide (Li2S), phosphorus sulfide (for example, phosphorus pentasulfide (P2S5)), elemental phosphorus, elemental sulfur, sodium sulfide, hydrogen sulfide, lithium halide (for example, LiI, LiBr, LiCl) and sulfides of the elements represented by the above M (for example, SiS2, SnS, GeS2).
[0116] The ratio of Li2S to P2S5 in the Li-PS glass and Li-PS glass ceramics is preferably 60:40 to 90:10, and more preferably 68:32 to 78:22, in terms of the molar ratio of Li2S:P2S5. By setting the ratio of Li2S to P2S5 within this range, the lithium ion conductivity can be improved. Specifically, the lithium ion conductivity can be preferably set to 1×10 -4 S / cm or more, more preferably 1×10 -3 S / cm or more. There is no specific upper limit, but it is actually 1×10 -1 S / cm or less.
[0117] As specific examples of sulfide-based inorganic solid electrolytes, combinations of raw materials are shown below. For example, Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-LiBr-P2S5, Li2S-Li2O-P2S5, Li2S-Li3PO4-P2S5, Li2S-P2S5-P2O5, Li2S-P2S5-SiS2, Li2S-P2S5-SiS2-LiCl, Li2S-P2S5-SnS, Li2S-P2S5-Al2 S3, Li2S-GeS2, Li2S-GeS2-ZnS, Li2S-Ga2S3, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Li2S-GeS2-Al2S3, Li2S-SiS2, Li2S-Al2S3, Li2S-SiS2-Al2S3, Li2S-SiS2-P2S5, Li2S-SiS2-P2S5-LiI, Li2S-SiS2-LiI, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li 10 GeP2S 12 Etc. Among them, the mixing ratio of each raw material is not limited. As a method for synthesizing a sulfide-based inorganic solid electrolyte material using such a raw material composition, for example, an amorphization method can be cited. As an amorphization method, for example, a mechanical grinding method, a solution method, and a melt quenching method can be cited. This is because it can be processed at room temperature, thereby simplifying the manufacturing process.
[0118] (ii) Oxide-based inorganic solid electrolytes
[0119] The oxide-based inorganic solid electrolyte is preferably a compound that contains oxygen atoms, has ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and has electron insulating properties.
[0120] The ionic conductivity of the oxide-based inorganic solid electrolyte is preferably 1×10 -6 S / cm or more, more preferably 5×10 -6 S / cm or more, particularly preferably 1×10 -5 S / cm or more. The upper limit is not particularly limited, but is actually 1×10 - 1 S / cm or less.
[0121] As specific examples of compounds, for example, Li xa Laya TiO3〔xa satisfies 0.3≤xa≤0.7, ya satisfies 0.3≤ya≤0.7.〕(LLT); Li xb La yb Zr zb M bb mb O nb (M bb is one or more elements selected from the group consisting of Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In and Sn. xb satisfies 5≤xb≤10, yb satisfies 1≤yb≤4, zb satisfies 1≤zb≤4, mb satisfies 0≤mb≤2, and nb satisfies 5≤nb≤20. ); Li xc B yc M cc zc O nc (M cc is one or more elements selected from C, S, Al, Si, Ga, Ge, In and Sn. xc satisfies 0<xc≤5, yc satisfies 0<yc≤1, zc satisfies 0<zc≤1, and nc satisfies 0<nc≤6. ); Li xd (Al, Ga) yd (Ti, Ge) zd Si ad P md O nd (xd satisfies 1≤xd≤3, yd satisfies 0≤yd≤1, zd satisfies 0≤zd≤2, ad satisfies 0≤ad≤1, md satisfies 1≤md≤7, and nd satisfies 3≤nd≤13.) (3-2xe) M ee xe D ee O(xe represents a number greater than or equal to 0 and less than or equal to 0.1, M ee Represents a divalent metal atom. ee represents a halogen atom or a combination of two or more halogen atoms. ); Li xf Si yf O zf (xf satisfies 1≤xf≤5, yf satisfies 0<yf≤3, zf satisfies 1≤zf≤10.) xg S yg O zg (xg satisfies 1≤xg≤3, yg satisfies 0<yg≤2, zg satisfies 1≤zg≤10.);Li3BO3;Li3BO3-Li2SO4;Li2O-B2O3-P2O5;Li2O-SiO2;Li6BaLa2Ta2O 12 ;Li3PO (4-3 / 2w) N w(w satisfies w<1); Li with LISICON (Lithium super ionic conductor) type crystal structure 3.5 Zn 0.25 GeO4; La with perovskite crystal structure 0.55 Li 0.35 TiO3; LiTi2P3O with NASICON (Natrium super ionic conductor) crystal structure 12 ;Li 1+xh+yh (Al, Ga) xh (Ti, Ge) 2-xh Si yh P 3-yh O 12 (xh satisfies 0≤xh≤1, yh satisfies 0≤yh≤1.); Li7La3Zr2O with garnet crystal structure 12 (LLZ) etc.
[0122] Furthermore, phosphorus compounds containing Li, P and O are also preferred. Examples thereof include lithium phosphate (Li3PO4); LiPON obtained by substituting a part of the oxygen element in lithium phosphate with nitrogen; LiPOD 1 (D 1 Preferably, it is one or more elements selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt and Au. ) etc.
[0123] In addition, LiA can also be preferably used 1 ON(A 1 It is one or more elements selected from Si, B, Ge, Al, C and Ga. ) etc.
[0124] (iii) Halide-based inorganic solid electrolytes
[0125] The halogenide-based inorganic solid electrolyte is preferably a compound containing halogen atoms and having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table and having electron insulating properties.
[0126] The halide inorganic solid electrolyte is not particularly limited, and examples thereof include LiCl, LiBr, LiI, and compounds such as Li3YBr6 and Li3YCl6 described in ADVANCED MATERIALS, 2018, 30, 1803075. Among them, Li3YBr6 and Li3YCl6 are preferred.
[0127] (iv) Hydride-based inorganic solid electrolytes
[0128] The hydride-based inorganic solid electrolyte is preferably a compound that contains hydrogen atoms and has ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table and has electron insulating properties.
[0129] The hydride-based inorganic solid electrolyte is not particularly limited, and examples thereof include LiBH4, Li4(BH4)3I, and 3LiBH4-LiCl.
[0130] The inorganic solid electrolyte is preferably in a particulate form in the inorganic solid electrolyte composition. The shape of the particle is not particularly limited, and may be flat, amorphous, etc., preferably spherical or granular. In the case where the inorganic solid electrolyte is in a particulate form, the particle size (volume average particle size) of the inorganic solid electrolyte is not particularly limited, and is preferably 0.01 μm or more, and more preferably 0.1 μm or more. As an upper limit, it is preferably 100 μm or less, and more preferably 50 μm or less.
[0131] The particle size of the inorganic solid electrolyte is determined according to the following steps. In a 20 mL sample bottle, the particles of the inorganic solid electrolyte are diluted with water (heptane is used in the case of substances unstable in water) to prepare a dispersion of 1 mass %. The diluted dispersion sample is irradiated with 1 kHz ultrasound for 10 minutes and then used in the test immediately. Using the dispersion sample, and using a laser diffraction / scattering particle size distribution measuring device LA-920 (product name, manufactured by HORIBA, Ltd.), 50 data readings are performed at a temperature of 25°C using a quartz colorimetric cell for measurement to obtain the volume average particle size. For other detailed conditions, please refer to the description in Japanese Industrial Standard (JIS) Z8828:2013 "Particle Size Analysis-Dynamic Light Scattering Method" as needed. Five samples are made for each level and their average value is adopted.
[0132] The method for adjusting the particle size is not particularly limited, and a known method can be applied, for example, a method using a common pulverizer or classifier can be cited. As a pulverizer or classifier, for example, a mortar, a ball mill, a sand mill, a vibrating ball mill, a satellite ball mill, a planetary ball mill, and a rotary airflow type jet mill or a sieve can be preferably used. When pulverizing, wet pulverization in which a dispersion medium such as water or methanol coexists can be performed. In order to set the desired particle size, it is preferably classified. Classification is not particularly limited, and a sieve, a wind classifier, etc. can be used for classification. Regarding classification, dry and wet methods can be used simultaneously.
[0133] The inorganic solid electrolyte may contain one kind or two or more kinds.
[0134] The content of the inorganic solid electrolyte in the inorganic solid electrolyte composition is not particularly limited. From the perspective of adhesion and dispersibility, the solid content is preferably 50% by mass or more, more preferably 70% by mass or more, and particularly preferably 90% by mass or more in 100% by mass of the solid component. As the upper limit, from the same viewpoint, it is preferably 99.9% by mass or less, more preferably 99.5% by mass or less, and particularly preferably 99% by mass or less.
[0135] When the inorganic solid electrolyte-containing composition contains an active material described below, the content of the inorganic solid electrolyte in the inorganic solid electrolyte-containing composition is preferably such that the total content of the active material and the inorganic solid electrolyte is within the above range.
[0136] In the present invention, solid content refers to the components that do not volatilize or evaporate when the inorganic solid electrolyte composition is dried for 2 hours at 100°C under atmospheric pressure (0.10 MPa). Typically, it refers to the components other than the dispersion medium (D) described later. In addition, when referred to as the content in the total solid content, it means the content in the total mass of the solid content of 100% by mass.
[0137] <Polymer binder (B)>
[0138] The polymer binder (B) contained in the inorganic solid electrolyte composition of the present invention is formed by comprising a polymer satisfying the above-mentioned mass average molecular weight (condition (1)). The polymer contained in the polymer binder (B) and forming the polymer binder (B) (also referred to as a binder-forming polymer) is not particularly limited as long as it satisfies the above-mentioned mass average molecular weight (condition (1)).
[0139] (Constitutional components of binder-forming polymer)
[0140] If the focus is on its constituent components, the binder-forming polymer preferably has one or more constituent components (I) containing functional groups. When the binder-forming polymer contains two or more constituent components (I) containing functional groups, the upper limit of the number of types is not particularly limited, and can be, for example, 5.
[0141] - Functional group-containing constituent (I) -
[0142] The functional group-containing component (I) is a component having at least one functional group selected from the following functional group group (I), and allows the polymer binder (B) to exhibit adsorptivity or adhesion to solid particles such as inorganic solid electrolytes.
[0143] The functional group-containing component (I) may have at least one (one type) of functional group, and usually preferably has 1 to 3 types of functional groups.
[0144] The functional group-containing constituent (I) has a functional group directly or via a linking group on a partial structure incorporated into the main chain of the binder-forming polymer.
[0145] In the functional group-containing constituent (I), the partial structure incorporated into the main chain is not uniquely determined according to the type of the binder-forming polymer (main chain), but can be appropriately selected. For example, in the case of a chain polymer, a carbon chain (carbon-carbon bond) can be cited.
[0146] As a linking group L that links the partial structure incorporated into the main chain to the functional group P , is not particularly limited, and examples thereof include alkylene groups (preferably having 1 to 12 carbon atoms, more preferably 1 to 6, and further preferably 1 to 3), alkenylene groups (preferably having 2 to 6 carbon atoms, more preferably 2 to 3), arylene groups (preferably having 6 to 24 carbon atoms, more preferably 6 to 10), oxygen atoms, sulfur atoms, imino groups (-NR N -:R N represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms. ), a carbonyl group, a phosphate linking group (-OP(OH)(O)-O-), a phosphonic acid linking group (-P(OH)(O)-O-), or a group related to a combination thereof. As the linking group L P , preferably containing a -CO-O- group or a -CO-N(R N )-base (R N As described above. ) and alkylene groups. Wherein, the linking group L P It is preferred not to remove R from the functional group selected from the functional group group (I) I The obtained group.
[0147] In the present invention, the number of atoms constituting the linking group is preferably 1 to 36, more preferably 1 to 30, and further preferably 1 to 24. The number of linked atoms of the linking group is preferably 16 or less, more preferably 12 or less, and further preferably 10 or less. The lower limit is 1 or more. The above-mentioned number of linked atoms refers to the minimum number of atoms linking the specified structural parts. For example, in the case of -OC(=O)-CH2-CH2-S-, the number of atoms constituting the linking group is 10 and the number of linked atoms is 5.
[0148] <Functional group (I)>
[0149] Ester group (-CO-OR I 、-O-CO-R I ), carboxyl (-CO-OH), dicarboxylic acid, carbonate (-O-CO-OR I ), thioester group (-CS-OR I、-CO-SR I 、-CS-SR I ), thiocarbonate group (-O-CO-OR I A group in which at least one oxygen atom is replaced by a sulfur atom), an amide group (-CO-NR NI -R I ), carbamate group (-NR NI -CO-OR I ), urea (-NR NI -CO-NR NI -R I ), imido group
[0150] The chemical formula described in parentheses after the functional group name above represents the chemical structure of the group.
[0151] In addition, ester groups are included in thiocarbonate groups and carbamate groups, but the -CO-OR I The amide group is not interpreted as an ester group. Also, the amide group is included in the urea group, but the -CO-NR NI -R I The group formed by the cleavage of the dicarboxylic acid group or its anhydride group can contain an ester group (-CO-OR I ), carboxyl group, amide group, etc., but they are not interpreted as separate functional groups, but are collectively interpreted as groups formed by the cleavage of dicarboxylic acid groups or their anhydride groups.
[0152] Among the above functional groups, R I represents a hydrogen atom, a substituent or a polymer chain. I R I represents a substituent or a polymer chain. I The substituent of is not particularly limited, and for example, a group selected from the substituent Z described below can be cited, and an alkyl group is preferred. In particular, R bonded to an ester group I A combination of a short-chain alkyl group having 1 to 4 carbon atoms and a long-chain alkyl group having 5 to 24 carbon atoms is preferred. I The polymer chain is not particularly limited, and examples thereof include the polymer chain P described below. C . Can be used as R I The substituent or polymer chain (constituent included in the polymer chain) may further have a substituent. The substituent that may be further possessed is not particularly limited, and examples thereof include a group selected from the substituent Z described later, preferably an alkoxy group, a hydroxyl group, a carboxyl group, a sulfonic acid group (sulfo group), a phosphoric acid group, a phosphonic acid group, etc.
[0153] R in the above functional groups NIrepresents a hydrogen atom or a substituent. NI The substituents of are not particularly limited, and for example, a group selected from the substituent Z described below can be cited, and an alkyl group is preferred. NI It can be the same or different.
[0154] As a dicarboxylic acid group, it is not particularly limited, and includes a group formed by removing one or more hydrogen atoms from a dicarboxylic anhydride (for example, a group represented by the following formula (2a)) and a constituent itself formed by copolymerization of a polymerizable dicarboxylic anhydride as a polymerizable compound (for example, a constituent represented by the following formula (2b)), and further includes a group formed by the reaction of a dicarboxylic anhydride with an active hydrogen compound and the acid anhydride group being cleaved. As a group formed by removing one or more hydrogen atoms from a dicarboxylic anhydride, it is preferably a group formed by removing one or more hydrogen atoms from a cyclic dicarboxylic anhydride. As a dicarboxylic anhydride, for example, non-cyclic dicarboxylic anhydrides such as acetic anhydride, propionic anhydride, and benzoic anhydride, maleic anhydride, phthalic anhydride, fumaric acid, succinic anhydride, itaconic anhydride, and the like can be cited. As a polymerizable dicarboxylic anhydride, it is not particularly limited, and dicarboxylic anhydrides having an unsaturated bond in the molecule can be cited, preferably polymerizable cyclic dicarboxylic anhydrides. Specifically, maleic anhydride, itaconic anhydride, and the like can be cited. Examples of the dicarboxylic anhydride group include a group represented by the following formula (2a) and a constituent represented by the following formula (2b), but the present invention is not limited thereto. In each formula, * represents a bonding position.
[0155] The active hydrogen compound is not particularly limited as long as it is a compound that reacts with a dicarboxylic anhydride group, and examples thereof include alcohol compounds, amine compounds, thiol compounds, and a polymer chain P described below. C Compounds (e.g., chain transfer agents and polymer chains P C reactants) etc.
[0156] [Chemical formula 1]
[0157]
[0158] Polymer chain P C The polymer chain is not particularly limited, and a common polymer can be used, for example, a chain composed of a step-polymerization polymer or a chain-polymerization polymer described later. In the present invention, a chain composed of a chain-polymerization polymer is preferred, a polymer chain composed of a (meth)acrylic polymer, a polymer chain composed of a vinyl polymer is more preferred, and a polymer chain composed of a (meth)acrylic polymer is further preferred. When the polymer chain contains two or more constituent components, the bonding method of the constituent components is not particularly limited, and may be random, alternating, or blocky.
[0159] The polymer chain composed of a (meth)acrylic polymer is not particularly limited, and preferably has a constituent component derived from a (meth)acrylic compound (M1) described later, or a constituent component derived from a vinyl compound (M2) described later. Among them, a polymer chain having one or more constituent components derived from a (meth)acrylic ester compound is more preferred, and a polymer chain having a constituent component derived from an alkyl (meth)acrylate compound is further preferred. The alkyl (meth)acrylate compound preferably contains an ester compound of an alkyl group having 4 or more carbon atoms (preferably 6 or more carbon atoms), and can further contain an ester compound of a short-chain alkyl group having 3 or less carbon atoms. The short-chain alkyl group may further have the above-mentioned substituent.
[0160] With polymer chain P C The terminal bonding group is not particularly limited, and a suitable group can be obtained by a polymerization method, a polymerization termination method, etc. For example, a hydrogen atom, an alkyl group, an aryl group, a hydroxyl group, a chain transfer agent residue, an initiator residue, etc. can be cited. From the perspective of dispersion characteristics, an alkyl group (preferably having 1 to 20 carbon atoms, more preferably 4 to 20) can be cited. The group may further have a substituent, but is preferably unsubstituted.
[0161] Polymer chain P C The number average molecular weight can be appropriately determined as the number average molecular weight (including the linking group P) in the measurement method described later. P ), preferably 200 or more, more preferably 1,000 to 100,000, further preferably 1,000 to 50,000, and particularly preferably 2,000 to 20,000.
[0162] In the above functional groups, the polymer chain P C Preferably via the linking group P P bonding. That is, R I Preferably, the linking group P P and polymer chain P C As the linking group P P , is not particularly limited, and preferably includes the above-mentioned linking group L P Among them, as the linking group P P , more preferably a group composed of an alkylene group, an arylene group, a carbonyl group, an oxygen atom, a sulfur atom and an imino group, further preferably a group composed of an alkylene group, an arylene group, a carbonyl group, an oxygen atom, a sulfur atom and an imino group, and particularly preferably a group containing a -CO-O- group or a -CO-N(R N )-base (R N As described above. ) and alkylene groups.
[0163] In addition, as the linking group P PPreferably, the polymer chain P C The chain transfer agent, polymerization initiator, etc. used in the synthesis of the chain transfer agent is not particularly limited, and examples thereof include mercaptoacetic acid, 2-mercaptopropionic acid, 3-mercaptopropionic acid, 3-mercaptoisobutyric acid, 2-mercaptoethanol, 6-mercapto-1-hexanol, 2-aminoethanethiol, and 2-aminoethanethiol hydrochloride. C The functional group-containing constituent (I) includes, for example, a constituent in which a structural part derived from a chain transfer agent or the like is bonded to a structural part derived from a (meth)acrylic compound (M1) or a dicarboxylic acid group that reacts with the chain transfer agent. As a constituent in which a structural part derived from a chain transfer agent or the like is bonded to a structural part derived from a (meth)acrylic compound (M1), for example, a polymer chain P C A constituent component formed by bonding to a partial structure incorporated into the main chain via a -CO-O-alkylene-X-CO-(X)n-alkylene-S- group (for example, polymer M-6 synthesized in the examples). Here, X represents an oxygen atom or -NH-, and n is 0 or 1. In addition, as a constituent component formed by bonding a structural part derived from a chain transfer agent or the like and a structural part derived from a dicarboxylic acid group, for example, a polymer chain P C A constituent component in which a dicarboxylic acid group obtained by a ring-opening addition reaction via a chain transfer agent or the like is bonded to a partial structure incorporated in the main chain (for example, polymer M-4 synthesized in Examples).
[0164] The imide group is not particularly limited, and examples thereof include groups in which oxygen atoms bonded to two carboxyl groups in the above-mentioned dicarboxylic anhydride group are substituted with nitrogen atoms.
[0165] The carboxyl group and the dicarboxylic acid group may form a salt, and examples of the salt include various metal salts, ammonium salts, and amine salts.
[0166] The compound into which the functional group-containing constituent component (I) is introduced (sometimes referred to as a polymerizable compound having a functional group (I)) is not particularly limited, and examples thereof include compounds having at least one carbon-carbon unsaturated bond and a functional group. For example, a compound comprising a carbon-carbon unsaturated bond and a functional group directly bonded, a compound comprising a carbon-carbon unsaturated bond and a functional group bonded via a linking group L P The functional group itself contains a carbon-carbon unsaturated bond, and further the compound whose functional group itself contains a carbon-carbon unsaturated bond (for example, the above-mentioned polymerizable cyclic carboxylic acid anhydride). As the polymerizable compound having the functional group (I), specifically, there can be mentioned the (meth)acrylic compound (M1) or vinyl compound (M2) described later, or a compound having the functional group (I) introduced into these compounds (M1) or (M2).
[0167] -Composition ingredients (AM)-
[0168] The pressure-sensitive adhesive-forming polymer also preferably has one or two or more constituent components (AM) derived from a (meth)acrylate compound.
[0169] The constituent (AM) is not particularly limited, and may be a constituent derived from the (meth)acrylic compound (M1) described later. In addition, the constituent (AM) is one type of the constituent (I) containing a functional group, which corresponds to a constituent containing a functional group in which an ester group selected from the functional group group (I) is directly bonded to a partial structure incorporated in the main chain.
[0170] -Other components (Z)-
[0171] The binder-forming polymer may contain one or two or more components (referred to as other components (Z)) that are not components (I) or components (AM) containing a functional group.
[0172] The other components (Z) are not particularly limited, and examples thereof include components derived from the vinyl compound (M2) described below, and components necessary for forming various polymer main chains.
[0173] The content of each constituent component in the binder-forming polymer is not particularly limited and can be determined by appropriately considering the physical properties of the entire polymer, and is, for example, set within the following ranges.
[0174] The content of each component in the binder-forming polymer is set, for example, within the following range so that the total content of all components becomes 100% by mass.
[0175] When the binder-forming polymer has a plurality of specific components, the content of the components is defined as the total content.
[0176] The content of the functional group-containing constituent (I) is not particularly limited and can be appropriately adjusted in consideration of dispersion characteristics, etc. The content of the functional group-containing constituent (I) is, for example, preferably 1 to 100% by mass, more preferably 10 to 100% by mass, and further preferably 50 to 100% by mass relative to the total content of all constituents. In addition, when the binder-forming polymer has the above-mentioned constituent (AM), the content of the constituent (AM) is also included in the content of the functional group-containing constituent (I).
[0177] The content of the constituent component (AM) is not particularly limited and can be appropriately determined according to the type of the adhesive forming polymer. For example, when the adhesive forming polymer is a (meth) acrylic polymer, the content relative to the total content of all the constituent components is 50% by mass or more, and the preferred content is as described in the (meth) acrylic polymer described later. On the other hand, when the adhesive forming polymer is a polymer other than a (meth) acrylic polymer, the content of the constituent component (AM) relative to the total content of all the constituent components is preferably 1 to 49% by mass, and more preferably 1 to 20% by mass.
[0178] The content of other components (Z) is not particularly limited and can be a balance obtained by subtracting the contents of the above-mentioned components (I) and (AM) from the total content of all components, and is, for example, preferably 0 to 50% by mass, more preferably 0 to 20% by mass.
[0179] (Binder-forming polymer morphology)
[0180] The form and type of the binder-forming polymer are not particularly limited, and various known polymers can be used.
[0181] The primary structure (bonding form of constituent components) of the binder-forming polymer is not particularly limited, and any bonding form such as a random structure, a block structure, an alternating structure, or a graft structure may be adopted.
[0182] As the binder-forming polymer, for example, a polymer having a polymer chain having at least one bond selected from a carbamate bond, a urea bond, an amide bond, an imide bond, and an ester bond, or a carbon-carbon double bond in the main chain can be preferably cited. In the present invention, a carbon-carbon double bond polymer chain refers to a polymer chain formed by polymerization of carbon-carbon double bonds (ethylenically unsaturated groups), specifically, a polymer chain formed by polymerization of monomers having carbon-carbon unsaturated bonds (homopolymerization or copolymerization).
[0183] As long as the above-mentioned bonds are included in the main chain of the polymer, they are not particularly limited, and can be included in the constituent components (repeating units) and / or included as bonds connecting different constituent components. In addition, the above-mentioned bonds included in the main chain are not limited to one type, and can be two or more types, preferably 1 to 6 types, and more preferably 1 to 4 types. In this case, the bonding method of the main chain is not particularly limited, and can randomly have more than two types of bonds, or can be a segmented main chain such as a segment having a specific bond and a segment having other bonds.
[0184] Examples of polymers having a urethane bond, urea bond, amide bond, imide bond or ester bond in the main chain include polyurethane, polyurea, polyamide, polyimide, polyester, polysiloxane and other stepwise polymerization (polycondensation, polyaddition or addition condensation) polymers or copolymers thereof. The copolymer may be a block copolymer having the above polymers as chain segments or a random copolymer in which the constituent components constituting two or more polymers of the above polymers are randomly bonded.
[0185] As the polymer having a polymer chain with a carbon-carbon double bond in the main chain, chain polymers such as fluoropolymers (fluorinated polymers), hydrocarbon polymers, vinyl polymers, (meth)acrylic polymers can be cited, preferably (meth)acrylic polymers. The polymerization method of these chain polymers is not particularly limited, and they can be any of block copolymers, alternating copolymers, and random copolymers, preferably random copolymers.
[0186] As a (meth) acrylic polymer, a polymer composed of a (co)polymer containing 50% by mass or more of a constituent derived from a (meth) acrylic compound can be cited. Here, in the case where the above-mentioned functional group-containing constituent (I) is a constituent derived from a (meth) acrylic compound (a constituent of a monoester obtained by reacting a dicarboxylic acid anhydride group with an active hydrogen-containing compound.), the content of each constituent is included in the content of the constituent derived from the (meth) acrylic compound. The content of the constituent derived from the (meth) acrylic compound can also be set to the same as the content of the above-mentioned functional group-containing constituent (I), more preferably 60% by mass or more, and further preferably 70% by mass or more. The upper limit content can also be set to 100% by mass, but can also be set to 97% by mass or less. As a (meth) acrylic polymer, it is further preferably a copolymer with a vinyl compound (M2) other than a (meth) acrylic compound (M1). In this case, the content of the constituent component derived from the vinyl compound (M2) is 50% by mass or less, preferably 3 to 40% by mass, and more preferably 3 to 30% by mass.
[0187] Examples of hydrocarbon polymers include polyethylene, polypropylene, natural rubber, polybutadiene, polyisoprene, polystyrene, polystyrene-butadiene copolymers, styrene-based thermoplastic elastomers, polybutene, acrylonitrile-butadiene copolymers or hydrogenated (hydrogenated) polymers thereof, copolymers with compounds copolymerizable with (meth)acrylic compounds (M1), vinyl compounds (M2) and the like, and copolymers containing a constituent component (I) containing a functional group. The styrene-based thermoplastic elastomer or its hydrogenated product is not particularly limited, and examples thereof include styrene-ethylene-butylene-styrene block copolymer (SEBS), styrene-isoprene-styrene block copolymer (SIS), hydrogenated SIS, styrene-butadiene-styrene block copolymer (SBS), hydrogenated SBS, styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS), styrene-ethylene-propylene-styrene block copolymer (SEPS), styrene-butadiene rubber (SBR), hydrogenated styrene-butadiene rubber (HSBR), and random copolymers corresponding to the above block copolymers such as SEBS, etc. In the present invention, the hydrocarbon polymer is preferably a polymer having no unsaturated group (e.g., 1,2-butadiene constituent) bonded to the main chain from the perspective of suppressing the formation of chemical crosslinks.
[0188] As fluoropolymers, for example, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), copolymers of polyvinylidene fluoride and hexafluoropropylene (PVDF-HFP), copolymers of polyvinylidene fluoride, hexafluoropropylene and tetrafluoroethylene (PVDF-HFP-TFE), copolymers with compounds copolymerizable with (meth)acrylic compounds (M1), vinyl compounds (M2) and the like, and copolymers containing constituent component (I) containing a functional group can also be cited.
[0189] In PVDF-HFP, the copolymerization ratio of PVDF to HFP [PVDF:HFP] (mass ratio) is not particularly limited, and is preferably 9:1 to 4:6, and more preferably 9:1 to 7:3 from the viewpoint of adhesion. In PVDF-HFP-TFE, the copolymerization ratio of PVDF, HFP and TFE [PVdF:HFP:TFE] (mass ratio) is not particularly limited, and is preferably 20 to 60:10 to 40:5 to 30, and more preferably 25 to 50:10 to 35:10 to 25.
[0190] As the (meth)acrylic compound (M1), there can be mentioned (meth)acrylic acid compounds, (meth)acrylic ester compounds, (meth)acrylamide compounds, (meth)acrylonitrile compounds, etc. Among them, (meth)acrylic ester compounds are preferred. As the (meth)acrylic ester compound, for example, (meth)acrylic alkyl ester compounds, (meth)acrylic aryl ester compounds, etc. can be mentioned, and (meth)acrylic alkyl ester compounds are preferred. The number of carbon atoms of the alkyl group constituting the (meth)acrylic alkyl ester compound is not particularly limited, and for example, it can be set to 1 to 24. From the perspective of dispersion characteristics and adhesion, it is preferably 3 to 20, more preferably 4 to 16, and further preferably 6 to 14. The number of carbon atoms of the aryl group constituting the aryl ester is not particularly limited, and for example, it can be set to 6 to 24, preferably 6 to 10, and more preferably 6. In the (meth)acrylamide compound, the nitrogen atom of the amide group can be substituted by an alkyl group or an aryl group.
[0191] The vinyl compound (M2) is not particularly limited, and is preferably a vinyl compound that can be copolymerized with the (meth) acrylic compound (M1), for example, aromatic vinyl compounds such as styrene compounds, vinyl naphthalene compounds, vinyl carbazole compounds, vinyl imidazole compounds, and vinyl pyridine compounds, as well as allyl compounds, vinyl ether compounds, vinyl ester compounds (for example, vinyl acetate compounds), itaconic acid dialkyl compounds, the above-mentioned polymerizable cyclic dicarboxylic acid anhydrides, etc. As the vinyl compound, for example, the "vinyl monomer" described in Japanese Patent Publication No. 2015-88486 can be cited.
[0192] The (meth)acrylic compound (M1) and the vinyl compound (M2) may have a substituent. The substituent is not particularly limited, and may be a group selected from the substituent Z described below, preferably a group that can be used as the above R I Preferred substituents are:
[0193] The binder-forming polymer is preferably a polymer having a polymer chain with carbon-carbon double bonds in the main chain. From the perspective of being able to balance dispersion characteristics, resistance and cycle characteristics at a high level, a hydrocarbon polymer, a vinyl polymer, or a (meth)acrylic polymer is more preferred, and a (meth)acrylic polymer is further preferred.
[0194] The binder-forming polymer may have a substituent. The substituent is not particularly limited, and preferably includes a group selected from the following substituents Z, and preferably a substituent that does not correspond to a functional group included in the functional group group (I).
[0195] -Substituent Z-
[0196] Examples thereof include alkyl groups (preferably alkyl groups having 1 to 20 carbon atoms, for example, methyl, ethyl, isopropyl, tert-butyl, pentyl, heptyl, 1-ethylpentyl, benzyl, 2-ethoxyethyl, 1-carboxymethyl, etc.), alkenyl groups (preferably alkenyl groups having 2 to 20 carbon atoms, for example, vinyl, allyl, oleyl, etc.), alkynyl groups (preferably alkynyl groups having 2 to 20 carbon atoms, for example, ethynyl, butadiynyl, phenylethynyl, etc.), cycloalkyl groups (preferably cycloalkyl groups having 3 to 20 carbon atoms, for example, cyclopropyl, cyclopentyl, cyclohexyl, 4-methylcyclohexyl, etc.) and the like. When referred to as an alkyl group, it generally refers to a cycloalkyl group, which is described separately herein. ), an aryl group (preferably an aryl group having 6 to 26 carbon atoms, for example, phenyl, 1-naphthyl, 4-methoxyphenyl, 2-chlorophenyl, 3-methylphenyl, etc.), an aralkyl group (preferably an aralkyl group having 7 to 23 carbon atoms, for example, benzyl, phenethyl, etc.), a heterocyclic group (preferably a heterocyclic group having 2 to 20 carbon atoms, more preferably a 5- or 6-membered heterocyclic group having at least one oxygen atom, sulfur atom, or nitrogen atom. The heterocyclic group includes an aromatic heterocyclic group and an aliphatic heterocyclic group. For example, a tetrahydropyranyl group, a tetrahydrofuranyl group, a 2-pyridyl 4-pyridyl, 2-imidazolyl, 2-benzimidazolyl, 2-thiazolyl, 2-oxazolyl, pyrrolidonyl, etc.), alkoxy (preferably an alkoxy group having 1 to 20 carbon atoms, for example, methoxy, ethoxy, isopropoxy, benzyloxy, etc.), aryloxy (preferably an aryloxy group having 6 to 26 carbon atoms, for example, phenoxy, 1-naphthyloxy, 3-methylphenoxy, 4-methoxyphenoxy, etc.), heterocyclic oxy (a group in which an -O- group is bonded to the above heterocyclic group), alkoxycarbonyl (preferably an alkoxycarbonyl group having 2 to 20 carbon atoms, for example, ethoxycarbonyl, 2-ethylhexyloxycarbonyl , dodecyloxycarbonyl, etc.), aryloxycarbonyl (preferably aryloxycarbonyl having 7 to 26 carbon atoms, for example, phenoxycarbonyl, 1-naphthyloxycarbonyl, 3-methylphenoxycarbonyl, 4-methoxyphenoxycarbonyl, etc.), heterocyclic oxycarbonyl (a group in which an -O-CO- group is bonded to the above heterocyclic group), amino (preferably amino, alkylamino, arylamino having 0 to 20 carbon atoms, for example, amino (-NH2), N,N-dimethylamino, N,N-diethylamino, N-ethylamino, anilino, etc.), sulfamoyl (preferably sulfamoyl having 0 to 20 carbon atoms, for example, N,N-dimethylsulfamoyl, N-phenylsulfamoyl, etc.), acyl (including alkylcarbonyl, alkenylcarbonyl, alkynylcarbonyl, arylcarbonyl, heterocyclic carbonyl, preferably acyl having 1 to 20 carbon atoms, for example, acetyl, propionyl, butyryl, octanoyl, hexadecanoyl, acryloyl, methacryloyl, crotonyl, benzoyl, naphthoyl, nicotinoyl, etc.), acyloxy (including alkylcarbonyloxy, alkenylcarbonyloxy, alkynylcarbonyloxy, heterocyclic carbonyloxy, preferably acyloxy having 1 to 20 carbon atoms, for example, acetyloxy, propionyloxy, butyryloxy, octanoyl, hexadecanoyl, acryloyl, methacryloyl, crotonyl, benzoyl, naphthoyl, nicotinoyl, etc.), The present invention also includes aryloxy (preferably aryloxy having 7 to 23 carbon atoms, for example, benzoyloxy, naphthoyloxy, etc.), carbamoyl (preferably carbamoyl having 1 to 20 carbon atoms, for example, N,N-dimethylcarbamoyl, N-phenylcarbamoyl, etc.), acylamino (preferably acylamino having 1 to 20 carbon atoms, for example, acetylamino, benzylamino, etc.), alkylthio (preferably alkylthio having 1 to 20 carbon atoms, for example, methylthio, ethylthio, isopropylthio, benzylthio, etc.), arylthio a thio group (preferably an arylthio group having 6 to 26 carbon atoms, for example, a phenylthio group, a 1-naphthylthio group, a 3-methylphenylthio group, a 4-methoxyphenylthio group, etc.), a heterocyclic thio group (a group in which a -S- group is bonded to the above heterocyclic group), an alkylsulfonyl group (preferably an alkylsulfonyl group having 1 to 20 carbon atoms, for example, a methylsulfonyl group, an ethylsulfonyl group, etc.), an arylsulfonyl group (preferably an arylsulfonyl group having 6 to 22 carbon atoms, for example, a benzenesulfonyl group, etc.), an alkylsilyl group (preferably an alkylsilyl group having 1 to 20 carbon atoms, for example, a monomethylsilyl group, a dimethylsilyl group, a trimethylsilyl group, etc.), silyl, triethylsilyl, etc.), arylsilyl (preferably an arylsilyl having 6 to 42 carbon atoms, for example, triphenylsilyl, etc.), alkoxysilyl (preferably an alkoxysilyl having 1 to 20 carbon atoms, for example, monomethoxysilyl, dimethoxysilyl, trimethoxysilyl, triethoxysilyl, etc.), aryloxysilyl (preferably an aryloxysilyl having 6 to 42 carbon atoms, for example, triphenoxysilyl, etc.), phosphoryl (preferably a phosphoric acid group having 0 to 20 carbon atoms, for example, -OP(=O)(R, P ) 2), a phosphono group (preferably a phosphono group having 0 to 20 carbon atoms, for example, -P(=O)(R P ) 2), phosphinyl group (preferably a phosphinyl group having 0 to 20 carbon atoms, for example, -P(R P ) 2), phosphonic acid group (preferably a phosphonic acid group having 0 to 20 carbon atoms, for example, -PO(OR P ) 2), sulfo group (sulfonic acid group), carboxyl group, hydroxyl group, sulfanyl group, cyano group, halogen atom (such as fluorine atom, chlorine atom, bromine atom, iodine atom, etc.). Pis a hydrogen atom or a substituent (preferably a group selected from the substituent Z).
[0197] Furthermore, each group listed in the substituent Z may be further substituted by the substituent Z described above.
[0198] The above-mentioned alkyl, alkylene, alkenyl, alkenylene, alkynyl and / or alkynylene groups may be cyclic or chain-shaped, and may be straight-chain or branched.
[0199] The binder-forming polymer can be synthesized by selecting a raw material compound and polymerizing the raw material compound by a known method.
[0200] The method for incorporating the functional group is not particularly limited, and examples thereof include a method of copolymerizing a compound having a functional group, a method of using a polymerization initiator or chain transfer agent having (producing) the above functional group, a method of utilizing a polymer reaction, an ene reaction to a double bond, an ene thiol reaction, or an ATRP (Atom Transfer Radical Polymerization) polymerization method using a copper catalyst, etc. In addition, the functional group can be introduced by using a functional group present in the main chain, side chain or terminal of the polymer as a reaction point. For example, the functional group can be introduced by using a compound having a functional group and various reactions with a dicarboxylic anhydride group in a polymer chain, etc.
[0201] Specific examples of the binder-forming polymer include the polymers synthesized in the examples, but the present invention is not limited to these.
[0202] - Physical properties or characteristics of the binder-forming polymer or polymer binder, etc. -
[0203] The polymer binder or binder-forming polymer used in the present invention preferably has the following physical properties or characteristics, etc.
[0204] The polymer binder preferably has the property (solubility) of being dissolved in the dispersion medium (D) contained in the inorganic solid electrolyte composition of the present invention. The polymer binder (B) in the inorganic solid electrolyte composition generally exists in the inorganic solid electrolyte composition in a state dissolved in the dispersion medium, although it depends on its content. Thus, the effect of improving the dispersibility of the solid particles can be further improved, and the dispersion characteristics, operability, low resistance and cycle characteristics can be improved in a balanced manner.
[0205] In the present invention, the polymer binder (B) being dissolved in the dispersion medium (D) means that the polymer binder (B) is dissolved in the dispersion medium (D) in the inorganic solid electrolyte composition, for example, it means that the solubility in the following solubility measurement of the polymer binder (B) is 50% or more. The polymer binder (B) is not limited to a mode in which all the polymer binder (B) is dissolved in the dispersion medium (D) in the inorganic solid electrolyte composition, including a mode in which a part of the polymer binder (B) exists insoluble. On the contrary, the polymer binder is not dissolved in the dispersion medium (insoluble) means that the solubility is less than 50% by mass in the solubility measurement.
[0206] The solubility measurement method is the same as the solubility measurement method in the compound (A), except that the polymer binder (B) (solid) is used instead of the compound (A).
[0207] In the present invention, the solubility of the polymer binder (B) in the dispersion medium (D) can be appropriately imparted by the type of binder-forming polymer, the composition of the binder-forming polymer (the type and content of the constituent components), the mass average molecular weight of the binder-forming polymer, the type of the above-mentioned functional group, and the combination with the dispersion medium.
[0208] In the case where the polymer binder (B) is not dissolved in the dispersion medium, the polymer binder (B) is usually dispersed in the form of particles. The shape of the polymer binder at this time is not particularly limited, and can be flat, amorphous, etc., preferably spherical or granular. In this case, in the inorganic solid electrolyte composition, the particle size of the particulate polymer binder is not particularly limited, preferably more than 1nm, more preferably more than 10nm, and more preferably more than 30nm. As an upper limit, it is preferably less than 5μm, more preferably less than 1μm, and more preferably less than 500nm. The particle size of the polymer binder can be measured in the same manner as the particle size of the above-mentioned inorganic solid electrolyte. The particle size of the polymer binder can be adjusted, for example, by the type of dispersion medium, the composition of the binder-forming polymer, etc.
[0209] The water concentration of the binder (binder-forming polymer) is preferably 100 ppm (mass basis) or less. The binder may be crystallized and dried, or the binder liquid may be used as it is.
[0210] The binder-forming polymer is preferably amorphous. In the present invention, the polymer is "amorphous", which typically means that no endothermic peak due to crystal melting is observed when measured at the glass transition temperature.
[0211] The binder-forming polymer may be a non-crosslinked polymer or a crosslinked polymer. Furthermore, when the polymer is crosslinked by heating or applying a voltage, the molecular weight may be greater than the above molecular weight. Preferably, the mass average molecular weight of the binder-forming polymer is within the above range when the all-solid-state secondary battery is first used.
[0212] The binder-forming polymer contained in the polymer binder may be one or more than two. Furthermore, as long as the effect of the above-mentioned binder-forming polymer is not impaired, the polymer binder may include other polymers, etc. As other polymers, polymers commonly used as binders for all-solid-state secondary batteries can be used without particular restrictions.
[0213] The polymer binder contained in the inorganic solid electrolyte composition may be one kind or two or more kinds.
[0214] The content of the polymer binder in the inorganic solid electrolyte composition is not particularly limited. From the perspective of dispersion characteristics, ion conductivity, and adhesion, it is preferably 0.1 to 6.0 mass %, more preferably 0.3 to 5.0 mass %, and further preferably 0.4 to 2.5 mass %, based on 100 mass % of the solid content.
[0215] In the present invention, the mass ratio of the total mass (total amount) of the inorganic solid electrolyte and the active material to the mass of the polymer binder in 100 mass% of the solid content [(mass of the inorganic solid electrolyte + mass of the active material) / (total mass of the polymer binder)] is preferably in the range of 1,000 to 1. Further, the ratio is more preferably 500 to 2, and further preferably 100 to 10.
[0216] <Compound (A)>
[0217] The compound (A) contained in the inorganic solid electrolyte-containing composition of the present invention has at least one functional group selected from the functional group group (a) described later (condition (2)).
[0218] As described above, it is considered that the compound (A) exhibits a function of enhancing the adsorptivity between the polymer binder (B) and the solid particles.
[0219] The type of functional group possessed by compound (A) is not particularly limited, and may be one or more, and preferably one from the perspective of being able to stably adsorb on solid particles. Furthermore, the number of functional groups possessed by compound (A) is not particularly limited, and may be, for example, 1 to 4, and preferably 1 to 2, and more preferably 1 from the perspective of being able to stably adsorb on solid particles. Compound (A) is particularly preferably a compound having one functional group.
[0220] [Functional group (a)]
[0221] Hydroxyl, amino, carboxyl, sulfonic acid (-S(=O)2OR C ), phosphate group (-OP (=O) (OR C )2), phosphonic acid group (-P(=O)(OR C )2), cyano, thiol (-SH), sulfinyl (-S(=O)R C )
[0222] R in functional group C represents a hydrogen atom or a substituent, preferably a hydrogen atom. C The substituents of are not particularly limited, and for example, groups selected from the above-mentioned substituents Z can be cited, for example, preferably hydrocarbon groups such as alkyl, alkenyl, alkynyl, and aryl. The two R C It can be the same or different.
[0223] The amino group, sulfonic acid group (sulfo group), phosphoric acid group (phosphoryl group) and phosphonic acid group are not particularly limited, and their meanings are the same as the corresponding groups of the above-mentioned substituent Z. Among them, the number of carbon atoms of the amino group is more preferably 0 to 12, further preferably 0 to 6, and particularly preferably 0 to 2. Hydroxyl, amino, carboxyl and thiol groups can form salts, and when Rc is a hydrogen atom, sulfonic acid, phosphoric acid, phosphonic acid and sulfanyl groups can also form salts. Among them, each functional group included in the functional group group (a) preferably does not have a metal element. For example, when the above-mentioned functional groups form salts, organic cations can be mentioned as cations, and specifically, ammonium cations, alkylammonium cations, etc. can be mentioned.
[0224] In addition, the amino group preferably does not constitute an amide group together with the carbonyl group.
[0225] Among the functional groups mentioned above, the functional group possessed by the compound (A) is preferably a hydroxyl group, a carboxyl group, a sulfonic acid group, a phosphonic acid group, or a thiol group, and more preferably a thiol group.
[0226] Compound (A) can be an inorganic compound such as polysiloxane, or an organic compound such as an aliphatic compound or an aromatic compound, preferably an aliphatic compound. Aliphatic compounds and aromatic compounds can each have at least one heteroatom such as oxygen, nitrogen, sulfur, or phosphorus, but are preferably aliphatic hydrocarbon compounds and aromatic hydrocarbon compounds. Furthermore, aliphatic compounds and aromatic compounds can each be a linear structure, a branched structure, or a cyclic structure (including monocyclic and polycyclic) or any one of the structures formed by combining them, preferably not including a cyclic structure in the molecule, more preferably a linear structure or a branched structure. The cyclic structure includes a monocyclic structure and a polycyclic structure. Furthermore, compound (A) can be a polymer compound such as a polymer, but is preferably a non-polymerizable low molecular compound.
[0227] In compound (A), the basic skeleton to which the functional group is bonded (the residue obtained by removing the functional group from compound (A)) is not particularly limited, and an appropriate group can be selected. The residue may be any of a group derived from an inorganic compound, an aliphatic group, and an aromatic group, and may be a monovalent group or a divalent or higher group, preferably a monovalent group. For example, as a monovalent residue, an alkyl group, an alkenyl group, an alkynyl group, an aryl group (preferably having 6 to 24 carbon atoms, more preferably 6 to 10 carbon atoms), a siloxane group (-Si(R S )2-O-), a carbonyl group or a group involved in a combination with these groups, and groups involved in a combination with these groups and an oxygen atom, a sulfur atom, an imino group (-NR N -:R N The residue having a valency of 2 or more may be a group obtained by removing a desired number of hydrogen atoms from a monovalent residue, or an oxygen atom, a sulfur atom, an imino group (-NR N -:R N represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms. ) etc. As the residue, an alkyl group, an alkenyl group, an alkynyl group, an aryl group, or a group related to a combination thereof is preferred, an alkyl group, an alkenyl group, an alkynyl group, or a group related to a combination thereof is more preferred, and an alkyl group is further preferred.
[0228] Here, R in the siloxane group S represents a hydrogen atom or a substituent, preferably a substituent. S The substituent of is not particularly limited and may be a group selected from the above-mentioned substituent Z, preferably an alkyl group or an aryl group.
[0229] Each of the alkyl, alkenyl and alkynyl groups may be linear, branched or cyclic, but is preferably linear or branched, more preferably linear.
[0230] The number of carbon atoms constituting the alkyl group is not particularly limited and can be appropriately set, for example, it can be set to 1 to 24, preferably 3 to 20, more preferably 4 to 16, and further preferably 6 to 14 from the perspective of dispersion characteristics and adhesion. The number of carbon atoms constituting the alkenyl group and the alkynyl group is not particularly limited and can be appropriately set, for example, it can be set to 2 to 24, preferably 3 to 20, more preferably 4 to 16, and further preferably 6 to 14 from the perspective of dispersion characteristics and adhesion. The number of carbon atoms constituting the alkyl group, the alkenyl group, and the alkynyl group is particularly preferably the same as the number of carbon atoms of the terminal group (details will be described later) of the polymer that forms the polymer binder (B) used simultaneously with the compound (A). In addition, the number of carbon atoms of the substituents constituting each group is not included in the number of carbon atoms constituting each group.
[0231] Furthermore, in the groups involved in the combination, the number of groups or atoms combined is not particularly limited, but when compound (A) is a non-polymerizable low molecular weight compound, for example, it can be set to 2 to 200, preferably 2 to 100, and when compound (A) is a polymer, it can be set to 2 to 100. In particular, when compound (A) is a siloxane polymer, the degree of polymerization n of the siloxane is preferably an integer of 1 to 100, more preferably an integer of 5 to 50, and further preferably an integer of 10 to 30. The terminal group of the polymer is not particularly limited, and for example, R S1 -Si(R S )2-O-. R S1 The meaning of R S same.
[0232] In the group involved in the combination, the number of types of the combined groups or atoms is not particularly limited, and can be, for example, two or more, and is preferably two or three.
[0233] In compound (A), the residue obtained by removing the functional group can have different chemical structures relative to the atomic bonding of the main chain forming the polymer forming the adhesive and the side chain (partial structure) branched from the main chain, but preferably has the same chemical structure. Here, about the side chain of the residue of the compound (A) and the differences of the chemical structure, in the case of not including the following heteroatom linking groups in the side chain, it is set to the side chain as a whole, on the other hand, in the case of including the following heteroatom linking groups in the side chain, it is set to the terminal group bonded to the heteroatom linking group instead of the side chain as a whole. For example, in the polymer M-1 synthesized in the embodiment, phenyl is become for the styrene constituent, and the terminal group bonded to the ester group is become for each constituent derived from the (meth) acrylate compound. In addition, it is identical with respect to the chemical structure, and will be described later.
[0234] The heteroatom linking group possessed by the binder-forming polymer may be any linking group (bond) as long as it is composed of a heteroatom, and examples thereof include an oxygen atom (—O—), an imino group (—NR N -:R N It represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms. ), a sulfur atom (-S-), a carbonyl group (-CO-), a thiocarbonyl group (-CS-), or a group composed of these. The number of atoms or groups constituting the combined group is not particularly limited and can be set to 2 to 30, preferably 2 to 10. Specifically, as the heteroatom linking group, an oxygen atom, an imino group, a sulfur atom, an ester bond (-CO-O-), a carbonate bond (-O-CO-O-), an amide bond (-CO-NR N -), urethane bond (-NR N -CO-O-), urea bond (-NR N -CO-NR N Among them, ester bonds (-CO-O-), amide bonds (-CO-NR N -), urethane bond (-NR N -CO-O-), urea bond (-NR N -CO-NR N -), more preferably an ester bond (-CO-O-), an amide bond (-CO-NR N -).
[0235] In the binder-forming polymer, the heteroatom linking group in the partial structure that becomes the side chain (also referred to as the side chain forming partial structure) may be one or more. Furthermore, the total number of heteroatom linking groups in the side chain forming partial structure is not uniquely determined based on the type of the binder-forming polymer and the type of constituent components. For example, if it is a common constituent component without a polymer chain, it is preferred to have 1 to 3 heteroatom linking groups, and if it is a constituent component with a polymer chain, it is determined based on the degree of polymerization of the polymer chain and the molecular structure of the constituent component constituting the polymer chain.
[0236] The constituent having a heteroatom linking group is not particularly limited, and examples thereof include the above-mentioned constituent (I) containing a functional group, constituent (AM) and other constituent (Z). Specifically, constituents derived from (meth)acrylate compounds having an ester bond as a heteroatom linking group, constituents derived from (meth)acrylic acid amide compounds having an amide bond as a heteroatom linking group, and constituents having a tert-butyl acrylate bond as a heteroatom linking group in the polymer chain P can be cited. C The components of these components are included.
[0237] In the present invention, when the binder-forming polymer has a side chain and a terminal group for determining the difference in chemical structure with the residue of compound (A), the terminal group is preferably used. That is, in the present invention, the residue of compound (A) without the functional group may have a different chemical structure than the terminal group of the binder-forming polymer bonded to the heteroatom linking group, but more preferably has the same chemical structure (satisfying condition (5)).
[0238] It is believed that in the inorganic solid electrolyte composition of the present invention, if the compound (A) satisfies condition (5), the interaction with the polymer forming the polymer binder (B) is enhanced, and the dispersibility improvement effect of the polymer binder (D) on the solid particles and the adhesion to the solid particles can be further improved. As a result, without compromising the excellent operability, the dispersion characteristics, the suppression of resistance increase and the cycle characteristics can be achieved at a higher level in a balanced manner.
[0239] In the present invention, the residue obtained by removing the functional group from the compound (A) represents the above-mentioned basic skeleton. Wherein, in the case where the residue is more than divalent (the case where the compound (A) has more than two functional groups), for convenience, a hydrogen atom is added to the above-mentioned basic skeleton as a monovalent residue to judge the differences and similarities of the chemical structure with the terminal group. On the other hand, the terminal group bonded to the heteroatom linking group of the polymer constituting the polymer binder (B) refers to, in the case of a constituent having one heteroatom linking group in the side chain forming partial structure of one constituent, the terminal group bonded to the heteroatom linking group, in the case of having multiple heteroatom linking groups in the side chain forming partial structure of one constituent, refers to the terminal group bonded to the heteroatom linking group in the constituent, which is located at the farthest position (terminal side) relative to the partial structure incorporated into the main chain of the binder forming polymer. Here, in the case where a polymer chain containing a constituent having a heteroatom linking group is present in the side chain forming partial structure of one constituent, even if a heteroatom linking group is present in addition to the polymer chain, it means the terminal group bonded to the heteroatom linking group in the above constituent contained in the polymer chain. For example, the terminal groups in the polymer M-1 synthesized in the examples are three kinds: hexyl, 2-hydroxyethyl and methyl, and the terminal groups in the polymer M-4 are three kinds: phenyl, dodecyl and 2-hydroxyethyl.
[0240] The side chain and the terminal group cannot be uniquely determined based on the type of binder-forming polymer, its constituent components, etc., but in order to exhibit a strong interaction with the polymer binder (B) and to be able to balance the dispersion characteristics, resistance and cycle characteristics at a high level, it is preferably a group that does not have a group that is easily adsorbed to solid particles, for example, it is preferably a group that does not have a substituent, and it is preferably an unsubstituted hydrocarbon group (alkyl, alkenyl, alkynyl, aryl).
[0241] On the other hand, as described above, the residue of the compound (A) preferably has no substituent that inhibits the interaction with the polymer binder (B), such as a halogen atom, and is preferably an unsubstituted hydrocarbon group.
[0242] In the present invention, when there are multiple terminal groups in the polymer binder (B), as in the above-mentioned polymer M-1, the terminal group that is judged to be different from the chemical structure of the residue is set to a group without a substituent (unsubstituted terminal group) from the perspective of interaction, and when there are multiple unsubstituted terminal groups, it is set to be the terminal group with the largest molecular weight. For example, the terminal group that is judged to be different from the residue is a hexyl group in polymer M-1, a dodecyl group in polymer M-4, and an octyl group in polymer M-7.
[0243] The fact that the residue and the side chain or terminal group have different chemical structures means that the chemical structure of the residue is different from any one of the types of the groups (side chains) of the chemical structure of the side chain or terminal group, the number of carbon atoms constituting each group (side chain), and the presence or absence of a substituent. For example, as a combination of a residue and a side chain or terminal group having different chemical structures, there can be cited a combination in which the residue is an alkyl group and the side chain or terminal group is an aryl group, a combination in which the residue and the side chain or terminal group are alkyl groups and have different numbers of carbon atoms, a combination in which a residue having a substituent and an unsubstituted side chain or terminal group, etc. Among the combinations in which the chemical structures of the residue and the side chain or terminal group are different, it is preferred that the residue and the side chain or terminal group are the same type of group and have different numbers of carbon atoms.
[0244] On the other hand, the fact that a residue and a side chain or a terminal group have the same chemical structure means that the chemical structure of the residue and the chemical structure of the side chain or the terminal group are the same in terms of the type of each group (side chain), the number of carbon atoms constituting each group (side chain), and the presence or absence of a substituent.
[0245] The compound (A) is preferably a compound different from the dispersion medium (D) described below, and more preferably a compound different from the inorganic solid electrolyte (SE), the active material (AC) described below, the conductive aid, the lithium salt, the dispersant, etc. Examples of the compound (A) include aliphatic or aromatic alcohol compounds or thiol compounds, aliphatic or aromatic carboxylic acid compounds, aliphatic or aromatic sulfonate compounds, aliphatic or aromatic phosphate compounds, aliphatic or aromatic phosphonate compounds, aliphatic or aromatic cyano compounds, and aliphatic or aromatic sulfinyl compounds, preferably aliphatic alcohol compounds or thiol compounds, aliphatic carboxylic acid compounds, aliphatic sulfonate compounds, and aliphatic phosphonate compounds, and more preferably aliphatic thiol compounds.
[0246] Compound (A) may have a substituent other than the functional group included in the functional group group (a), and examples of the substituent include groups selected from the above-mentioned substituent Z, such as halogen atoms. When the hydrocarbon group that can be used as a residue has a halogen atom as a substituent, all hydrogen atoms in the hydrocarbon group may be substituted by halogen atoms, or part of the hydrogen atoms may be substituted by halogen atoms.
[0247] Furthermore, the compound (A) is preferably a compound that does not contain a metal element, and more preferably an organic compound that does not contain a metal element. In the present invention, the metal element generally refers to a metal element belonging to Group 1 to Group 17 in the periodic table, but the metal element that the compound (A) does not have is preferably a metal element belonging to Group 1, Group 2, Group 12 or Group 13, and more preferably a metal element belonging to Group 1 or Group 2.
[0248] Compound (A) can be a commercial product or a synthetic product. As a method for synthesizing compound (A), various known synthesis methods can be cited. In addition, it can also be synthesized using a raw material compound used in the synthesis of a binder-forming polymer, such as a (meth)acrylic compound (M1).
[0249] Specific examples of the compound (A) include the compounds prepared in Examples, but the present invention is not limited to these.
[0250] In the inorganic solid electrolyte composition of the present invention, the combination of the inorganic solid electrolyte (SE), the polymer binder (B) and the compound (A) can be appropriately combined without being particularly limited. For example, it is preferably a combination of the above-mentioned preferred compounds, and more preferably a combination of an inorganic solid electrolyte (SE), a polymer binder (B) dissolved in a dispersion medium (D), and a compound (A) having a molecular weight of less than 600 and satisfying the above-mentioned condition (5). If the type of compound is considered, a combination of a sulfide-based inorganic solid electrolyte as the inorganic solid electrolyte (SE), an acrylic polymer as the polymer binder (B), and an aliphatic thiol compound as the compound (A) is more preferred. In each of the above-mentioned preferred combinations, the content of the compound (A) is appropriately set within the following range, for example, but it is particularly preferably set to 10 ppm or more and 2.0×10 3 Below ppm.
[0251] The compound (A) contained in the inorganic solid electrolyte-containing composition may be one kind or two or more kinds.
[0252] In the inorganic solid electrolyte-containing composition of the present invention, the content of the compound (A) is not particularly limited, but is preferably 0.5 ppm or more and 2.0×10 3 ppm or less, more preferably 10 ppm or more and 2.0×10 3 ppm or less, more preferably 10 ppm or more and 1.0×10 3 ppm or less, particularly preferably 10 ppm or more and 6.0×10 2 ppm or less, and most preferably 10 ppm or more and 2.0×10 2 The content of the compound (A) is preferably 0.5 ppm or more and 1.0×10 4 ppm or less, more preferably 50 ppm or more and 1.0×10 4 ppm, more preferably 50 ppm or more and less than 5.0×10 3 ppm, particularly preferably 50 ppm or more and 3.0×10 3 ppm or less, and most preferably 50 ppm or more and 1.0×10 3 Below ppm.
[0253] On the other hand, the content of the compound (A) in the inorganic solid electrolyte composition is preferably 0.1 to 20 mass % relative to the polymer binder (B). From the perspective of being able to balance the dispersion characteristics, resistance and cycle characteristics at a high level, it is preferably 0.01 to 10 mass %, more preferably 0.1 to 10 mass %, further preferably 0.1 to 6 mass %, and particularly preferably 0.1 to 2 mass %.
[0254] The above content of compound (A) can be calculated based on the amount used when preparing the inorganic solid electrolyte composition, and can be calculated using the value obtained by measuring the content of each component in the inorganic solid electrolyte composition. For example, the content of compound (A) in the inorganic solid electrolyte composition can be measured using gas chromatography under the following method and conditions.
[0255] <Dispersion medium>
[0256] The inorganic solid electrolyte-containing composition of the present invention contains a dispersion medium (D) in which the above-mentioned components are dispersed or dissolved.
[0257] As such a dispersion medium, any organic compound that is liquid under the use environment may be mentioned, for example, various organic solvents, specifically, alcohol compounds, ether compounds, amide compounds, amine compounds, ketone compounds, aromatic hydrocarbon compounds, aliphatic hydrocarbon compounds, nitrile compounds, ester compounds, etc., among which ether compounds, amide compounds, ketone compounds, aromatic hydrocarbon compounds, aliphatic hydrocarbon compounds, and ester compounds are preferred.
[0258] The dispersion medium may be a non-polar dispersion medium (hydrophobic dispersion medium) or a polar dispersion medium (hydrophilic dispersion medium), and a non-polar dispersion medium is preferred from the perspective of being able to exhibit excellent dispersion characteristics. A non-polar dispersion medium generally indicates a property of low affinity for water, but in the present invention, for example, ester compounds, ketone compounds, ether compounds, aromatic hydrocarbon compounds, aliphatic hydrocarbon compounds, etc. may be cited.
[0259] Examples of the alcohol compound include methanol, ethanol, 1-propanol, 2-propanol, 2-butanol, ethylene glycol, propylene glycol, glycerol, 1,6-hexanediol, cyclohexanediol, sorbitol, xylitol, 2-methyl-2,4-pentanediol, 1,3-butanediol, and 1,4-butanediol.
[0260] Examples of the ether compound include alkylene glycols (diethylene glycol, triethylene glycol, polyethylene glycol, dipropylene glycol, etc.), alkylene glycol monoalkyl ethers (ethylene glycol monomethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, tripropylene glycol monomethyl ether, diethylene glycol monobutyl ether, etc.), alkylene glycol dialkyl ethers (ethylene glycol dimethyl ether, etc.), dialkyl ethers (dimethyl ether, diethyl ether, diisopropyl ether, dibutyl ether, etc.), and cyclic ethers (tetrahydrofuran, dioxane (including 1,2-, 1,3-, and 1,4-isomers), etc.).
[0261] Examples of the amide compound include N,N-dimethylformamide, N-methyl-2-pyrrolidone, 2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, ε-caprolactam, formamide, N-methylformamide, acetamide, N-methylacetamide, N,N-dimethylacetamide, N-methylpropaneamide, and hexamethylphosphoric triamide.
[0262] Examples of the amine compound include triethylamine, diisopropylethylamine, and tributylamine.
[0263] Examples of the ketone compound include acetone, methyl ethyl ketone, methyl isobutyl ketone (MIBK), cyclopentanone, cyclohexanone, cycloheptanone, dipropyl ketone, dibutyl ketone, diisopropyl ketone, diisobutyl ketone (DIBK), isobutyl propyl ketone, sec-butyl propyl ketone, amyl propyl ketone, and butyl propyl ketone.
[0264] Examples of the aromatic hydrocarbon compound include benzene, toluene, xylene, and perfluorotoluene.
[0265] Examples of the aliphatic hydrocarbon compound include hexane, heptane, octane, nonane, decane, dodecane, cyclohexane, methylcyclohexane, ethylcyclohexane, cycloheptane, cyclooctane, decalin, paraffin, gasoline, naphtha, kerosene, and light oil.
[0266] Examples of the nitrile compound include acetonitrile, propionitrile, and isobutyronitrile.
[0267] Examples of the ester compound include ethyl acetate, propyl acetate, butyl acetate, ethyl butyrate, propyl butyrate, isopropyl butyrate, butyl butyrate, isobutyl butyrate, butyl valerate, pentyl valerate, ethyl isobutyrate, propyl isobutyrate, isopropyl isobutyrate, isobutyl isobutyrate, propyl pivalate, isopropyl pivalate, butyl pivalate, and isobutyl pivalate.
[0268] In the present invention, among these, ether compounds, ketone compounds, aromatic hydrocarbon compounds, aliphatic hydrocarbon compounds, and ester compounds are preferred, and ester compounds, ketone compounds, aromatic hydrocarbon compounds, and ether compounds are more preferred.
[0269] The number of carbon atoms in the compound constituting the dispersion medium is not particularly limited, but is preferably 2 to 30, more preferably 4 to 20, further preferably 6 to 15, and particularly preferably 7 to 12.
[0270] From the perspective of the dispersion characteristics of the solid particles and, when a sulfide-based inorganic solid electrolyte is used as the inorganic solid electrolyte, the dispersion medium preferably has low polarity (low-polarity dispersion medium).
[0271] The boiling point of the dispersion medium under normal pressure (1 atmosphere) is not particularly limited, but is preferably 50° C. or higher, more preferably 70° C. or higher. The upper limit is preferably 250° C. or lower, more preferably 220° C. or lower.
[0272] The dispersion medium contained in the inorganic solid electrolyte composition may be one or more. As examples of dispersion media containing more than two kinds, xylene (a mixture of xylene isomers having a molar ratio of ortho-isomer: para-isomer: meta-isomer = 1:5:2), mixed xylene (a mixture of ortho-xylene, para-xylene, meta-xylene, and ethylbenzene), etc. may be cited.
[0273] The content of the dispersion medium in the inorganic solid electrolyte-containing composition is not particularly limited, and is, for example, preferably 10 to 80% by mass, more preferably 20 to 70% by mass, and further preferably 25 to 50% by mass.
[0274] <Active substances (AC)>
[0275] The inorganic solid electrolyte composition of the present invention may contain an active material capable of inserting and extracting ions of metals belonging to Group 1 or Group 2 of the periodic table. The active material is described below, and examples thereof include positive electrode active materials and negative electrode active materials.
[0276] In the present invention, an inorganic solid electrolyte composition containing an active material (positive electrode active material or negative electrode active material) may be referred to as an electrode composition (positive electrode composition or negative electrode composition).
[0277] (Positive electrode active material)
[0278] The positive electrode active material is an active material that can embed and de-embed metal ions belonging to Group 1 or Group 2 of the periodic table, preferably capable of reversibly embedding and releasing lithium ions. As long as the material has the above-mentioned characteristics, there is no particular limitation, and it can be a transition metal oxide, or an organic substance, sulfur, or other element that can be composited with Li.
[0279] Among them, as the positive electrode active material, it is preferred to use a transition metal oxide, and more preferably a transition metal element M a (one or more elements selected from Co, Ni, Fe, Mn, Cu and V) transition metal oxide. In addition, the element M may be mixed in the transition metal oxide. b (Metals other than lithium, elements of Group 1 (Ia) of the periodic table, elements of Group 2 (IIa), Al, Ga, In, Ge, Sn, Pb, Sb, Bi, Si, P, and B). As a mixed amount relative to the transition metal element M a The amount of Li / M is preferably 0 to 30 mol%. a The synthesis is performed by mixing so that the molar ratio of α and β may be 0.3 to 2.2.
[0280] Specific examples of transition metal oxides include (MA) transition metal oxides having a layered rock salt structure, (MB) transition metal oxides having a spinel structure, (MC) lithium-containing transition metal phosphate compounds, (MD) lithium-containing transition metal halophosphate compounds, and (ME) lithium-containing transition metal silicate compounds.
[0281] Specific examples of transition metal oxides having a layered rock salt structure (MA) include LiCoO2 (lithium cobalt oxide [LCO]), LiNi2O2 (lithium nickel oxide), LiNi 0.85 Co 0.10 Al 0.05O2 (nickel cobalt aluminum oxide [NCA]), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2 (lithium nickel manganese cobalt oxide [NMC]) and LiNi 0.5 Mn 0.5 O2 (lithium manganese nickel oxide).
[0282] Specific examples of the transition metal oxide (MB) having a spinel structure include LiMn2O4 (LMO), LiCoMnO4, Li2FeMn3O8, Li2CuMn3O8, Li2CrMn3O8 and Li2NiMn3O8.
[0283] As (MC) lithium-containing transition metal phosphate compounds, for example, there can be mentioned olivine-type iron phosphate salts such as LiFePO4 and Li3Fe2(PO4)3, pyrophosphate iron salts such as LiFeP2O7, cobalt phosphates such as LiCoPO4, and monoclinic NASICON-type vanadium phosphate salts such as Li3V2(PO4)3 (lithium vanadium phosphate).
[0284] Examples of the (MD) lithium-containing transition metal halophosphate compound include iron fluorophosphates such as Li2FePO4F, manganese fluorophosphates such as Li2MnPO4F, and cobalt fluorophosphates such as Li2CoPO4F.
[0285] Examples of the (ME) lithium-containing transition metal silicate compound include Li2FeSiO4, Li2MnSiO4, and Li2CoSiO4.
[0286] In the present invention, (MA) is preferably a transition metal oxide having a layered rock salt structure, and more preferably LCO or NMC.
[0287] The shape of the positive electrode active material is not particularly limited, but it is preferably in a particulate form in the composition containing an inorganic solid electrolyte. When the positive electrode active material is in a particulate form, the particle size (volume average particle size) of the positive electrode active material is not particularly limited. For example, it can be set to 0.1 to 50 μm. The particle size of the positive electrode active material particles can be adjusted in the same manner as the particle size of the above-mentioned inorganic solid electrolyte, and the determination method can also be determined in the same manner as the particle size of the inorganic solid electrolyte.
[0288] The positive electrode active material obtained by the calcination method can be used after being washed with water, an acidic aqueous solution, an alkaline aqueous solution, or an organic solvent.
[0289] The positive electrode active material contained in the inorganic solid electrolyte-containing composition of the present invention may be one kind or two or more kinds.
[0290] The content of the positive electrode active material in the inorganic solid electrolyte composition is not particularly limited, but is preferably 10 to 97% by mass, more preferably 30 to 95% by mass, further preferably 40 to 93% by mass, and particularly preferably 50 to 90% by mass, based on 100% by mass of the solid content.
[0291] (Negative electrode active material)
[0292] The negative electrode active material is an active material that can embed and deintercalate ions of metals belonging to Group 1 or Group 2 of the periodic table, preferably capable of reversibly embedding and releasing lithium ions. As long as the material has the above-mentioned characteristics, there is no particular limitation, and carbonaceous materials, metal oxides, metal composite oxides, lithium monomers, lithium alloys, negative electrode active materials that can form alloys with lithium (can be alloyed) can be cited. Among them, from the viewpoint of reliability, carbonaceous materials, metal composite oxides or lithium monomers can be preferably used. From the aspect of being able to increase the capacity of the all-solid-state secondary battery, it is preferably an active material that can be alloyed with lithium.
[0293] The carbonaceous material used as the negative electrode active material refers to a material substantially composed of carbon. For example, carbon black such as petroleum pitch, acetylene black (AB), graphite (natural graphite, artificial graphite such as vapor-grown graphite, etc.), and various synthetic resins such as PAN (polyacrylonitrile) resins or furfuryl alcohol resins are calcined and obtained. In addition, various carbon fiber types such as PAN carbon fiber, cellulose carbon fiber, pitch carbon fiber, vapor-grown carbon fiber, dehydrated PVA (polyvinyl alcohol) carbon fiber, lignin carbon fiber, glassy carbon fiber and activated carbon fiber, mesophase microspheres, graphite whiskers and flat graphite can also be cited.
[0294] These carbonaceous materials can also be divided into carbonaceous materials (also referred to as hard carbon) that are difficult to graphitize according to the degree of graphitization. And graphite-based carbonaceous materials. In addition, the carbonaceous material preferably has the surface spacing or density and crystallite size recorded in Japanese Patent Publication No. 62-22066, Japanese Patent Publication No. 2-6856, and Japanese Patent Publication No. 3-45473. Carbonaceous materials do not need to be a single material, and a mixture of natural graphite and artificial graphite recorded in Japanese Patent Publication No. 5-90844, and graphite with a coating layer recorded in Japanese Patent Publication No. 6-4516 can also be used.
[0295] As the carbonaceous material, hard carbon or graphite can be preferably used, and graphite is more preferable.
[0296] The oxide of the metal or semi-metal element used as the negative electrode active material is not particularly limited as long as it is an oxide that can occlude and release lithium, and examples thereof include oxides of metal elements (metal oxides), composite oxides of metal elements or composite oxides of metal elements and semi-metal elements (collectively referred to as metal composite oxides), and oxides of semi-metal elements (semi-metal oxides). As these oxides, amorphous oxides are preferred, and further preferred examples include chalcogenides, which are reaction products of metal elements and elements of Group 16 of the periodic table. In the present invention, semi-metal elements refer to elements that show properties intermediate between metal elements and non-semi-metal elements, and generally include six elements of boron, silicon, germanium, arsenic, antimony and tellurium, and further include three elements of selenium, polonium and astatine. In addition, amorphous means that a material having a wide scattering band with a vertex in the region of 20° to 40° at a 2θ value by an X-ray diffraction method using CuKα rays may also have crystalline diffraction lines. The strongest intensity of the crystalline diffraction line observed at a 2θ value of 40° to 70° is preferably 100 times or less, more preferably 5 times or less, the intensity of the diffraction line at the top of the wide scattering band observed at a 2θ value of 20° to 40°, and it is particularly preferred to have no crystalline diffraction line.
[0297] In the compound group including the above-mentioned amorphous oxides and chalcogenides, amorphous oxides of semimetallic elements or the above-mentioned chalcogenides are more preferred, and particularly preferred are (complex) oxides or chalcogenides formed by a single element or a combination of two or more elements selected from Groups 13 (IIIB) to 15 (VB) of the periodic table (e.g., Al, Ga, Si, Sn, Ge, Pb, Sb, and Bi). Specific examples of preferred amorphous oxides and chalcogenides include, for example, Ga2O3, GeO, PbO, PbO2, Pb2O3, Pb2O4, Pb3O4, Sb2O3, Sb2O4, Sb2O8Bi2O3, Sb2O8Si2O3, Sb2O5, Bi2O3, Bi2O4, GeS, PbS, PbS2, Sb2S3, or Sb2S5.
[0298] Preferred negative electrode active materials that can be used together with the amorphous oxides containing Sn, Si or Ge as the core include carbonaceous materials that can occlude and / or release lithium ions or lithium metal, lithium monomers, lithium alloys, and negative electrode active materials that can alloy with lithium.
[0299] From the perspective of high current density charge and discharge characteristics, the oxide of a metal or semimetal element, especially a metal (composite) oxide and the above-mentioned chalcogenide preferably contains at least one of titanium and lithium as a constituent component. As a metal composite oxide containing lithium (lithium composite metal oxide), for example, a composite oxide of lithium oxide and the above-mentioned metal (composite) oxide or the above-mentioned chalcogenide can be cited, and more specifically, Li2SnO2 can be cited.
[0300] The negative electrode active material, such as a metal oxide, preferably also contains titanium element (titanium oxide). Specifically, Li4Ti5O 12 (Lithium titanate [LTO]) is preferred because it has a small volume change when storing and releasing lithium ions, and therefore has excellent rapid charge and discharge characteristics, and can suppress electrode degradation and increase the life of the lithium ion secondary battery.
[0301] The lithium alloy used as the negative electrode active material is not particularly limited as long as it is an alloy commonly used as a negative electrode active material for secondary batteries. For example, lithium-aluminum alloys can be mentioned, and specifically, lithium-aluminum alloys formed by adding 10 mass % of aluminum to lithium as a base metal can be mentioned.
[0302] As for the negative electrode active material that can form an alloy with lithium, as long as it is a material that is usually used as a negative electrode active material for a secondary battery, it is not particularly limited. This active material has a large expansion and contraction caused by the charge and discharge of the all-solid-state secondary battery, and accelerates the decline in cycle characteristics, but the inorganic solid electrolyte composition of the present invention contains the above-mentioned polymer binder (B) and compound (A), so it is possible to suppress the decline in cycle characteristics. As such an active material, there can be cited (negative electrode) active materials (alloys, etc.) having silicon or tin elements, various metals such as Al and In, preferably a negative electrode active material (silicon-containing active material) having silicon elements that can achieve higher battery capacity, and more preferably a silicon-containing active material having a silicon content of more than 50 mol% of all constituent elements.
[0303] Generally, the negative electrode containing these negative electrode active materials (for example, Si negative electrode containing silicon-containing active materials, Sn negative electrode containing tin-containing active materials, etc.) can contain more Li ions than carbon negative electrodes (graphite and acetylene black, etc.). That is, the amount of Li ions contained per unit mass increases. Therefore, the battery capacity (energy density) can be increased. As a result, it has the advantage of being able to extend the battery driving time.
[0304] As active materials containing silicon elements, for example, silicon materials such as Si and SiOx (0<x≤1), and silicon-containing alloys (for example, LaSi2, VSi2, La-Si, Gd-Si, Ni-Si) or organized active materials (for example, LaSi2 / Si) containing titanium, vanadium, chromium, manganese, nickel, copper, lanthanum, etc., can be cited. In addition, active materials containing silicon elements and tin elements such as SnSiO3 and SnSiS3 can be cited. In addition, SiOx itself can be used as a negative electrode active material (semi-metallic oxide), and Si is generated by the operation of an all-solid-state secondary battery, so it can be used as a negative electrode active material (its precursor material) that can be alloyed with lithium.
[0305] Examples of negative electrode active materials containing tin include Sn, SnO, SnO2, SnS, SnS2, and the above-mentioned active materials containing silicon and tin. Also, composite oxides with lithium oxide, such as Li2SnO2, can be cited.
[0306] In the present invention, the above-mentioned negative electrode active material can be used without particular restrictions, but from the perspective of battery capacity, as the negative electrode active material, a negative electrode active material that can be alloyed with lithium is a preferred embodiment, among which the above-mentioned silicon material or silicon-containing alloy (alloy containing silicon element) is more preferred, and silicon (Si) or a silicon-containing alloy is further preferred.
[0307] The chemical formula of the compound obtained by the above calcination method can be calculated by using inductively coupled plasma (ICP) emission spectrometry as a measurement method and the mass difference of the powder before and after calcination as a simple method.
[0308] The shape of the negative electrode active material is not particularly limited, but is preferably in a particle shape in the composition containing an inorganic solid electrolyte. When the negative electrode active material is in a particle shape, the particle size of the negative electrode active material is not particularly limited, but is preferably 0.1 to 60 μm. The particle size of the negative electrode active material particles can be adjusted in the same manner as the particle size of the above-mentioned inorganic solid electrolyte, and the measurement method can also be measured in the same manner as the particle size of the inorganic solid electrolyte.
[0309] The negative electrode active material contained in the inorganic solid electrolyte-containing composition of the present invention may be one kind or two or more kinds.
[0310] The content of the negative electrode active material in the inorganic solid electrolyte composition is not particularly limited, but is preferably 10 to 90% by mass, more preferably 20 to 85% by mass, more preferably 30 to 80% by mass, and even more preferably 40 to 75% by mass based on 100% by mass of the solid content.
[0311] In the present invention, when the negative electrode active material layer is formed by charging the secondary battery, the ions of metals belonging to Group 1 or Group 2 of the periodic table generated in the all-solid-state secondary battery can be used instead of the negative electrode active material. The negative electrode active material layer can be formed by bonding the ions with electrons to precipitate them as metals.
[0312] (Encapsulation of active substances)
[0313] The surface of the positive electrode active material and the negative electrode active material can be coated with different metal oxides. As the surface coating agent, metal oxides containing Ti, Nb, Ta, W, Zr, Al, Si or Li can be cited. For example, titanate spinel, tantalum oxides, niobium oxides, lithium niobate compounds, etc. can be cited. Specifically, Li4Ti5O 12 , Li2Ti2O5, LiTaO3, LiNbO3, LiAlO2, Li2ZrO3, Li2WO4, Li2TiO3, Li2B4O7, Li3PO4, Li2MoO4, Li3BO3, LiBO2, Li2CO3, Li2SiO3, SiO2, TiO2, ZrO2, Al2O3, B2O3, etc.
[0314] Furthermore, the surface of the electrode including the positive electrode active material or the negative electrode active material may be surface-treated with sulfur or phosphorus.
[0315] Furthermore, before or after the above-mentioned surface coating, the surface of the particles of the positive electrode active material or the negative electrode active material may be subjected to a surface treatment using active light or active gas (plasma, etc.).
[0316] <Conductive additive>
[0317] The inorganic solid electrolyte-containing composition of the present invention may contain a conductive auxiliary agent.
[0318] There are no particular restrictions on the conductive aid, and any conductive aid known as a common conductive aid can be used. For example, it can be graphites such as natural graphite and artificial graphite, carbon blacks such as acetylene black, Ketjenblack, and furnace black, amorphous carbon such as needle coke, carbon fibers such as vapor-grown carbon fibers or carbon nanotubes, carbonaceous materials such as graphene or fullerene, or metal powders and metal fibers such as copper and nickel, or conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene, and polyphenylene derivatives.
[0319] In the present invention, when an active material and a conductive aid are used simultaneously, the following substances are used as conductive aids among the conductive aids: when the battery is charged and discharged, no insertion and release of ions (preferably Li ions) of metals belonging to Group 1 or Group 2 of the periodic table occur, and the conductive aids do not function as active materials. Therefore, among the conductive aids, those that can function as active materials in the active material layer when the battery is charged and discharged are classified as active materials rather than conductive aids. Whether or not to function as an active material when the battery is charged and discharged is not determined solely, but is determined by the combination with the active material.
[0320] The conductive aid is preferably in a particulate form in the inorganic solid electrolyte composition. When the conductive aid is in a particulate form, the particle size (volume average particle size) of the conductive aid is not particularly limited, and is, for example, preferably 0.02 to 1.0 μm, more preferably 0.03 to 0.5 μm. The particle size of the conductive aid can be adjusted in the same manner as the particle size of the inorganic solid electrolyte, and the determination method can also be determined in the same manner as the particle size of the inorganic solid electrolyte.
[0321] The conductive additive contained in the inorganic solid electrolyte composition may be one kind or two or more kinds.
[0322] When the inorganic solid electrolyte-containing composition of the present invention contains a conductive additive, the content of the conductive additive in the inorganic solid electrolyte-containing composition is preferably 0 to 10% by mass, more preferably 1 to 5% by mass, based on 100% by mass of the solid content.
[0323] <Lithium salt>
[0324] The inorganic solid electrolyte composition of the present invention also preferably contains a lithium salt (supporting electrolyte). As a lithium salt, it is preferably a lithium salt commonly used in such products, and there is no particular restriction, for example, preferably a lithium salt described in paragraphs 0082 to 0085 of Japanese Patent Publication No. 2015-088486. In the case where the inorganic solid electrolyte composition of the present invention includes a lithium salt, the content of the lithium salt is preferably 0.1 parts by mass or more, and more preferably 5 parts by mass or more, relative to 100 parts by mass of the solid electrolyte. As an upper limit, it is preferably 50 parts by mass or less, and more preferably 20 parts by mass or less.
[0325] <Dispersant>
[0326] In the inorganic solid electrolyte composition of the present invention, the above-mentioned polymer binder also functions as a dispersant, so it may not contain a dispersant other than the polymer binder, but may also contain a dispersant. As a dispersant, a dispersant commonly used in all-solid-state secondary batteries can be appropriately selected for use. Usually, it is preferred to use a compound with particle adsorption and spatial repulsion and / or electrostatic repulsion as the purpose.
[0327] <Other additives>
[0328] The inorganic solid electrolyte composition of the present invention can appropriately contain ionic liquids, thickeners, crosslinking agents (substances that undergo crosslinking reactions by free radical polymerization, polycondensation or ring-opening polymerization, etc.), polymerization initiators (substances that generate acids or free radicals by heat or light, etc.), defoamers, leveling agents, dehydrating agents, antioxidants, etc. as other ingredients in addition to the above-mentioned components. The ionic liquid is a liquid contained in order to further improve the ionic conductivity, and known liquids can be used without particular restrictions. In addition, polymers other than the above-mentioned binder-forming polymers, commonly used binders, etc. may be contained.
[0329] (Preparation of Inorganic Solid Electrolyte Composition)
[0330] The inorganic solid electrolyte composition of the present invention can be prepared as a mixture, preferably as a slurry, by mixing an inorganic solid electrolyte (SE), a polymer binder (B), a compound (A), a dispersion medium (D), and an appropriate conductive aid, a lithium salt, and any other ingredients, for example, with various commonly used mixers. Here, in the present invention, it is preferred that in addition to solid particles such as an inorganic solid electrolyte (SE) and a polymer binder (B), a compound (A) is also actively mixed. Thus, the adhesion between the solid particles and the polymer binder (B) can be enhanced. In addition, in the case of an electrode composition, an active material is further mixed.
[0331] The mixing method is not particularly limited, and the mixing can be carried out using a known mixer such as a ball mill, a bead mill, a planetary mixer, a scraper mixer, a roll mill, a kneader, a disk mill, a self-rotating and revolving mixer, or a narrow gap disperser.
[0332] The mixing conditions are not particularly limited. For example, the above-mentioned components can be mixed together or mixed in sequence. The mixing conditions are not particularly limited. As the mixing temperature, it is preferably set to a temperature at which at least compound (A) does not volatilize during mixing, for example, it can be set to 15 to 50°C. In addition, the rotation speed of the rotational revolving mixer can be set to 200 to 3,000 rpm. As the mixing atmosphere, it can be any one of atmospheric pressure, dry air (dew point below -20°C) and inert gas (for example, argon, helium, nitrogen). Since the inorganic solid electrolyte reacts easily with moisture, it is preferably mixed in dry air or inert gas.
[0333] The inorganic solid electrolyte-containing composition of the present invention is excellent in dispersion stability and can therefore be stored after preparation without having to prepare it each time it is used.
[0334] [Sheet for all-solid-state secondary batteries]
[0335] The sheet material for all-solid-state secondary batteries of the present invention is a sheet-like molded body capable of forming a structural layer of an all-solid-state secondary battery, and includes various modes according to its use. For example, a sheet material preferably used for a solid electrolyte layer (also referred to as a solid electrolyte sheet for an all-solid-state secondary battery), a sheet material preferably used for a laminate of an electrode or an electrode and a solid electrolyte layer (electrode sheet for an all-solid-state secondary battery), etc. can be cited. In the present invention, these various sheets are collectively referred to as sheets for all-solid-state secondary batteries.
[0336] In the present invention, each layer constituting the sheet for an all-solid-state secondary battery may have a single-layer structure or a multi-layer structure.
[0337] In the sheet for all-solid-state secondary battery, the solid electrolyte layer or the active material layer on the substrate is formed (composed) by the inorganic solid electrolyte composition of the present invention. The layer formed by the inorganic solid electrolyte composition of the present invention is formed by components derived from the inorganic solid electrolyte composition (excluding the dispersion medium (D)), and is usually firmly bonded (bonded) in a state where solid particles (inorganic solid electrolyte (SE), active material (AC), appropriate conductive auxiliary agent (AC)), polymer binder (B) and compound (A) are mixed.
[0338] The sheet for an all-solid-state secondary battery can improve the cycle characteristics and conductivity (reduce resistance) of the all-solid-state secondary battery by appropriately peeling off the substrate or directly incorporating it into the all-solid-state secondary battery.
[0339] The solid electrolyte sheet for all-solid-state secondary batteries of the present invention can be a sheet having a solid electrolyte layer, and can be a sheet having a solid electrolyte layer formed on a substrate, or a sheet having no substrate and formed by a solid electrolyte layer (a sheet formed by peeling off the substrate). In addition to the solid electrolyte layer, the solid electrolyte sheet for all-solid-state secondary batteries may also have other layers. As other layers, for example, protective layers (peel-off sheets), collectors, coatings, etc. can be cited. The solid electrolyte layer possessed by the solid electrolyte sheet for all-solid-state secondary batteries is preferably formed by the inorganic solid electrolyte composition of the present invention. The content of each component in the solid electrolyte layer is not particularly limited, and preferably has the same meaning as the content of each component in the solid component of the inorganic solid electrolyte composition of the present invention. The content of compound (A) in the solid electrolyte layer is the same as the content of 100% by mass of the solid component in the inorganic solid electrolyte composition of the present invention, and the content of the inorganic solid electrolyte (SE) or the polymer binder (B). The thickness of each layer constituting the solid electrolyte sheet for all-solid-state secondary batteries is the same as the thickness of each layer described in the all-solid-state secondary battery described later.
[0340] As a substrate, as long as it can support the solid electrolyte layer, it is not particularly limited, and can include the material described in the collector described later, organic materials, inorganic materials and other sheet-like bodies (flat bodies), etc. As organic materials, various polymers, etc. can be mentioned, specifically, polyethylene terephthalate, polypropylene, polyethylene and cellulose, etc. can be mentioned. As inorganic materials, for example, glass, ceramics, etc. can be mentioned.
[0341] The electrode sheet for all-solid-state secondary batteries of the present invention (also referred to as "electrode sheet" for short) can be an electrode sheet with an active material layer, and can be a sheet with an active material layer formed on a substrate (collector), or a sheet formed by an active material layer without a substrate (a sheet formed by peeling off a substrate). The electrode sheet is usually a sheet with a collector and an active material layer, but also includes a mode having a collector, an active material layer and a solid electrolyte layer in sequence, and a mode having a collector, an active material layer, a solid electrolyte layer and an active material layer in sequence. The solid electrolyte layer and active material layer possessed by the electrode sheet are preferably formed by the inorganic solid electrolyte composition of the present invention. The content of each component in the solid electrolyte layer or active material layer is not particularly limited, and preferably has the same meaning as the content of each component in the solid component of the inorganic solid electrolyte composition (electrode composition) of the present invention. In addition, the content of compound (A) in each layer is the same as the content of 100% by mass of the solid component in the inorganic solid electrolyte composition of the present invention, and the content of the inorganic solid electrolyte (SE) or the polymer binder (B). The content of the compound (A) in each layer can be measured by the method described in the examples. The thickness of each layer constituting the electrode sheet of the present invention is the same as the thickness of each layer described in the all-solid-state secondary battery described later. The electrode sheet may have the above-mentioned other layers.
[0342] When the solid electrolyte layer or the active material layer is not formed of the inorganic solid electrolyte composition of the present invention, it is formed of a common structural layer forming material.
[0343] In the sheet material for all-solid-state secondary batteries of the present invention, at least one layer in the structural layer is formed by the inorganic solid electrolyte composition of the present invention. Therefore, the sheet material for all-solid-state secondary batteries of the present invention has a structural layer with a flat surface that firmly bonds the solid particles uniformly arranged, although the interface resistance of the solid particles is suppressed from rising. Therefore, by assembling the structural layer into the all-solid-state secondary battery, the excellent cycle characteristics and low resistance (high conductivity) of the all-solid-state secondary battery can be achieved. In addition, in the electrode sheet for all-solid-state secondary batteries having an active material layer formed on the collector, the active material layer and the collector can be firmly fitted. In this way, the sheet material for all-solid-state secondary batteries of the present invention can be preferably used as a sheet component assembled as a structural layer of an all-solid-state secondary battery.
[0344] When the solid electrolyte layer or the active material layer is not formed of the inorganic solid electrolyte composition of the present invention, it is formed of a common structural layer forming material.
[0345] [Method for producing a sheet for an all-solid-state secondary battery]
[0346] The manufacturing method of the all-solid-state secondary battery sheet of the present invention is not particularly limited, and can be manufactured by forming the above-mentioned structural layer using the inorganic solid electrolyte composition of the present invention. It can be preferably cited that a film is formed on a substrate or a collector (or via another layer.) A method of forming a layer (coating dry layer) composed of an inorganic solid electrolyte composition is performed (coating dry). Thus, a sheet for all-solid-state secondary batteries having a substrate or a collector and a coating dry layer can be prepared. In particular, if the inorganic solid electrolyte composition (electrode composition) of the present invention is made into a film on the collector to make a sheet for all-solid-state secondary batteries, the close fit of the collector and the active material layer can be enhanced.
[0347] Here, the coating dried layer refers to a layer formed by coating the inorganic solid electrolyte-containing composition of the present invention and drying the dispersion medium (D) (i.e., a layer formed using the inorganic solid electrolyte-containing composition of the present invention and composed of a composition formed by removing the dispersion medium (D) from the inorganic solid electrolyte-containing composition of the present invention). As long as the effect of the present invention is not impaired, the dispersion medium (D) may remain in the structural layer and the coating dried layer, and the residual amount can be set to 3% by mass or less in each layer, for example.
[0348] In the method for producing the sheet for an all-solid-state secondary battery of the present invention, each step such as coating and drying will be described in the following method for producing an all-solid-state secondary battery.
[0349] In the method for producing the all-solid-state secondary battery sheet of the present invention, the applied dried layer obtained in the above manner may be pressurized. The pressurization conditions and the like will be described in the method for producing the all-solid-state secondary battery described later.
[0350] Furthermore, in the method for producing the sheet for an all-solid-state secondary battery of the present invention, the substrate, the protective layer (particularly the release sheet), and the like can also be peeled off.
[0351] [All-solid-state secondary battery]
[0352] The all-solid-state secondary battery of the present invention has a positive electrode active material layer, a negative electrode active material layer opposite to the positive electrode active material layer, and a solid electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer. As long as the all-solid-state secondary battery of the present invention has a solid electrolyte layer between the positive electrode active material layer and the negative electrode active material layer, the structure other than this is not particularly limited, for example, a known structure related to an all-solid-state secondary battery can be adopted. The positive electrode active material layer is preferably formed on the positive electrode collector and constitutes the positive electrode. The negative electrode active material layer is preferably formed on the negative electrode collector and constitutes the negative electrode. In the present invention, each structural layer (including the collector, etc.) constituting the all-solid-state secondary battery can be a single-layer structure or a multi-layer structure.
[0353] Preferably, at least one of the solid electrolyte layer, the negative electrode active material layer and the positive electrode active material layer is formed by the inorganic solid electrolyte composition of the present invention. In addition, it is also one of the preferred modes that the negative electrode active material layer and the positive electrode active material layer are both formed by the inorganic solid electrolyte composition of the present invention. In addition, with respect to the negative electrode (the laminate of the negative electrode collector and the negative electrode collector) and the positive electrode (the laminate of the positive electrode collector and the positive electrode collector), it is preferably any one of them, preferably the positive electrode is formed by the electrode sheet for the all-solid-state secondary battery of the present invention, and both are formed by the electrode sheet for the all-solid-state secondary battery of the present invention. It is also one of the preferred modes. In the present invention, it is also one of the preferred modes that all layers are formed by the inorganic solid electrolyte composition of the present invention. In addition, in the case where the active material layer or the solid electrolyte layer is not formed by the inorganic solid electrolyte composition of the present invention, it is possible to use known materials, compositions containing polymer binders used in the present invention, and the like.
[0354] The all-solid-state secondary battery of the present invention in which at least one of the solid electrolyte layer, the negative electrode active material layer and the positive electrode active material layer is formed of the inorganic solid electrolyte composition of the present invention exhibits low resistance and high ion conductivity, and thus can also extract a large current.
[0355] <Positive electrode active material layer, solid electrolyte layer, negative electrode active material layer>
[0356] In the solid electrolyte layer and active material layer formed by the inorganic solid electrolyte composition of the present invention, the types of components contained and their contents are preferably the same as the solid components of the inorganic solid electrolyte composition of the present invention. In addition, the content of compound (A) in each layer is the same as the content of 100% by mass of the solid component in the inorganic solid electrolyte composition of the present invention, and the content of the inorganic solid electrolyte (SE) or the polymer binder (B). The content of compound (A) in each layer can be determined by the method described in the embodiment.
[0357] The thickness of the negative electrode active material layer, the solid electrolyte layer, and the positive electrode active material layer is not particularly limited. Considering the size of a conventional all-solid-state secondary battery, the thickness of each layer is preferably 10 to 1,000 μm, more preferably 20 μm or more and less than 500 μm. In the all-solid-state secondary battery of the present invention, the thickness of at least one of the positive electrode active material layer and the negative electrode active material layer is further preferably 50 μm or more and less than 500 μm.
[0358] <Current Collector>
[0359] The positive electrode active material layer and the negative electrode active material layer may each include a current collector on the side opposite to the solid electrolyte layer. The positive electrode current collector and the negative electrode current collector are preferably electronic conductors.
[0360] In the present invention, either or both of the positive electrode current collector and the negative electrode current collector may be simply referred to as a current collector.
[0361] As the material for forming the positive electrode collector, in addition to aluminum, aluminum alloy, stainless steel, nickel and titanium, it is preferred to use a material in which the surface of aluminum or stainless steel has been treated with carbon, nickel, titanium or silver (a material with a thin film formed thereon), among which aluminum and aluminum alloy are more preferred.
[0362] As the material for forming the negative electrode collector, in addition to aluminum, copper, copper alloys, stainless steel, nickel and titanium, it is preferred to use a material whose surface has been treated with carbon, nickel, titanium or silver, and more preferably aluminum, copper, copper alloys and stainless steel.
[0363] The shape of the current collector is usually a film sheet, but a mesh, a perforated body, a lath body, a porous body, a foamed body, a molded body of a fiber group, or the like can also be used.
[0364] The thickness of the current collector is not particularly limited, but is preferably 1 to 500 μm. It is also preferred that the surface of the current collector be roughened by surface treatment.
[0365] <Other structures>
[0366] In the present invention, functional layers or components may be appropriately inserted or disposed between or outside the negative electrode collector, the negative electrode active material layer, the solid electrolyte layer, the positive electrode active material layer, and the positive electrode collector.
[0367] <Housing>
[0368] The all-solid-state secondary battery of the present invention can be directly used as an all-solid-state secondary battery with the above structure according to the purpose, but in order to make it into the form of a dry cell, it is preferably further encapsulated in an appropriate shell for use. The shell can be a metallic shell or a resin (plastic) shell. In the case of using a metallic shell, for example, a shell made of aluminum alloy or stainless steel can be cited. It is preferred that the metallic shell is divided into a positive electrode side shell and a negative electrode side shell and electrically connected to the positive electrode collector and the negative electrode collector respectively. The shell on the positive electrode side and the shell on the negative electrode side are preferably integrated by joining with a gasket to prevent short circuit.
[0369] <Preferred embodiment of all-solid-state secondary battery>
[0370] Below, reference Figure 1 , an all-solid-state secondary battery according to a preferred embodiment of the present invention is described, but the present invention is not limited thereto.
[0371] Figure 1 Schematically showing a cross-sectional view of an all-solid-state secondary battery (lithium-ion secondary battery) according to a preferred embodiment of the present invention. The all-solid-state secondary battery 10 of this embodiment has a negative electrode collector 1, a negative electrode active material layer 2, a solid electrolyte layer 3, a positive electrode active material layer 4, and a positive electrode collector 5 in order when viewed from the negative electrode side. Each layer is in contact with each other and has an adjacent structure. By adopting this structure, electrons (e) are supplied to the negative electrode side during charging. - ) and accumulate lithium ions (Li + On the other hand, during discharge, the lithium ions (Li + ) returns to the positive electrode side, and supplies electrons to the working portion 6. In the example shown in the figure, a bulb is modeled at the working portion 6, and the bulb is lit by discharge.
[0372] In will have Figure 1 When the all-solid-state secondary battery with the layer structure shown is placed in a 2032-type button battery case 11 (for example, refer to Figure 2 ), the all-solid-state secondary battery is sometimes referred to as an all-solid-state secondary battery laminate 12, and a battery (button type) produced by placing the all-solid-state secondary battery laminate 12 in a 2032 type button battery shell 11 is called an all-solid-state secondary battery 13 for the purpose of distinction.
[0373] (Positive electrode active material layer, solid electrolyte layer, negative electrode active material layer)
[0374] In the all-solid-state secondary battery 10, the positive electrode active material layer 4, the solid electrolyte layer 3 and the negative electrode active material layer 2 are all formed by the inorganic solid electrolyte composition of the present invention. The inorganic solid electrolyte (SE), polymer binder (B) and compound (A) contained in the positive electrode active material layer 4, the solid electrolyte layer 3 and the negative electrode active material layer 2 can be the same or different from each other. In addition, the conductive additives contained in the positive electrode active material layer 4 and the negative electrode active material layer 2 can be the same or different from each other.
[0375] In the present invention, either or both of the positive electrode active material layer and the negative electrode active material layer are referred to as active material layer or electrode active material layer. Also, either or both of the positive electrode active material and the negative electrode active material are referred to as active material or electrode active material.
[0376] The solid electrolyte layer contains an inorganic solid electrolyte (SE) having ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, the above-mentioned polymer binder (B), the above-mentioned compound (A), and any of the above-mentioned components within the range that does not impair the effects of the present invention, and usually does not contain a positive electrode active material and / or a negative electrode active material.
[0377] The positive electrode active material layer and the negative electrode active material layer respectively contain an inorganic solid electrolyte (SE) having ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, the above-mentioned polymer binder (B), the above-mentioned compound (A), an active material (AC), preferably a conductive aid and any of the above-mentioned components within the range that does not impair the effects of the present invention.
[0378] In the all-solid-state secondary battery 10, the negative electrode active material layer can be set as a lithium metal layer. As the lithium metal layer, there can be cited a layer formed by stacking or molding lithium metal powder, lithium foil, and lithium vapor-deposited film. Regardless of the thickness of the negative electrode active material layer, for example, the thickness of the lithium metal layer can be set to 1 to 500 μm.
[0379] In the present invention, when the structural layer is formed from the inorganic solid electrolyte composition of the present invention, an all-solid secondary battery having excellent cycle characteristics and low resistance can be realized.
[0380] (Current Collector)
[0381] The positive electrode current collector 5 and the negative electrode current collector 1 are respectively as described above.
[0382] In the case where the all-solid secondary battery 10 has a structural layer other than the structural layer formed of the inorganic solid electrolyte composition of the present invention, a layer formed of a known structural layer forming material can also be applied.
[0383] Furthermore, each layer may be configured as a single layer or as a multi-layer layer.
[0384] [Manufacturing of all-solid-state secondary batteries]
[0385] The all-solid-state secondary battery can be manufactured by a conventional method. Specifically, the all-solid-state secondary battery can be manufactured by forming the above-mentioned layers using the inorganic solid electrolyte composition of the present invention.
[0386] Specifically, the all-solid-state secondary battery of the present invention can be manufactured by a method (a method for manufacturing a sheet for an all-solid-state secondary battery of the present invention) including (via) the following steps, wherein the inorganic solid electrolyte composition of the present invention is appropriately coated on a substrate (for example, a metal foil serving as a current collector) to form a coating (perform film formation).
[0387] More specifically, an inorganic solid electrolyte composition containing a positive electrode active material as a positive electrode material (positive electrode composition) is applied and dried on a metal foil as a positive electrode collector to form a positive electrode active material layer to make a positive electrode sheet for an all-solid-state secondary battery. Next, a solid electrolyte layer is formed by applying and drying an inorganic solid electrolyte composition for forming a solid electrolyte layer on the positive electrode active material layer. In addition, an inorganic solid electrolyte composition containing a negative electrode active material as a negative electrode material (negative electrode composition) is applied and dried on the solid electrolyte layer to form a negative electrode active material layer. By stacking a negative electrode collector (metal foil) on the negative electrode active material layer, an all-solid-state secondary battery having a structure in which a solid electrolyte layer is sandwiched between the positive electrode active material layer and the negative electrode active material layer can be obtained. It can also be encapsulated in a housing to make a desired all-solid-state secondary battery.
[0388] Furthermore, an all-solid-state secondary battery can be manufactured by forming a negative electrode active material layer, a solid electrolyte layer, and a positive electrode active material layer on a negative electrode current collector in the reverse manner of the formation method of each layer and stacking a positive electrode current collector.
[0389] As other methods, the following methods can be cited. That is, a positive electrode sheet for an all-solid-state secondary battery is prepared in the above manner. In addition, an inorganic solid electrolyte composition containing a negative electrode active material as a negative electrode material (negative electrode composition) is applied and dried on a metal foil as a negative electrode collector to form a negative electrode active material layer to prepare a negative electrode sheet for an all-solid-state secondary battery. Then, on the active material layer of any one of these sheets, a solid electrolyte layer is formed in the above manner. In addition, on the solid electrolyte layer, the other of the positive electrode sheet for an all-solid-state secondary battery and the negative electrode sheet for an all-solid-state secondary battery is stacked in such a manner that the solid electrolyte layer is in contact with the active material layer. In this way, an all-solid-state secondary battery can be manufactured.
[0390] In addition, as other methods, the following methods can be cited. That is, a positive electrode sheet for an all-solid-state secondary battery and a negative electrode sheet for an all-solid-state secondary battery are prepared in the above manner. In addition, a solid electrolyte sheet for an all-solid-state secondary battery consisting of a solid electrolyte layer is prepared by coating a substrate with an inorganic solid electrolyte composition. In addition, the solid electrolyte layer peeled off from the substrate is sandwiched in a manner such that a positive electrode sheet for an all-solid-state secondary battery and a negative electrode sheet for an all-solid-state secondary battery are laminated. In this way, an all-solid-state secondary battery can be manufactured.
[0391] In addition, in the above manner, a positive electrode sheet for an all-solid-state secondary battery or a negative electrode sheet for an all-solid-state secondary battery and a solid electrolyte sheet for an all-solid-state secondary battery are made. Then, the positive electrode sheet for an all-solid-state secondary battery or the negative electrode sheet for an all-solid-state secondary battery and the solid electrolyte sheet for an all-solid-state secondary battery are overlapped and pressurized in a state where the positive electrode active material layer or the negative electrode active material layer is in contact with the solid electrolyte layer. In this way, the solid electrolyte layer is transferred to the positive electrode sheet for an all-solid-state secondary battery or the negative electrode sheet for an all-solid-state secondary battery. Thereafter, the solid electrolyte layer obtained by peeling off the substrate of the solid electrolyte sheet for an all-solid-state secondary battery and the negative electrode sheet for an all-solid-state secondary battery or the positive electrode sheet for an all-solid-state secondary battery (so that the negative electrode active material layer or the positive electrode active material layer is in contact with the solid electrolyte layer) are overlapped and pressurized. In this way, an all-solid-state secondary battery can be manufactured. The pressurization method and pressurization conditions in the method are not particularly limited, and can be applied to the method and pressurization conditions described in the pressurization process described later.
[0392] The solid electrolyte layer and the like are formed, for example, by pressure-molding an inorganic solid electrolyte composition and the like on a substrate or an active material layer under pressure conditions described later.
[0393] In the above-mentioned production method, the inorganic solid electrolyte-containing composition of the present invention may be used in any one of the inorganic solid electrolyte-containing composition, the positive electrode composition, and the negative electrode composition, or may be used in all the compositions.
[0394] In the case where a solid electrolyte layer or an active material layer is formed by a composition other than the inorganic solid electrolyte composition of the present invention, the material thereof may include a commonly used composition, etc. In addition, when manufacturing an all-solid-state secondary battery, a negative electrode active material layer is not formed, but ions of metals belonging to Group 1 or Group 2 of the periodic table accumulated in the negative electrode collector by initialization or charging during use described later are combined with electrons and precipitated as metal on the negative electrode collector, etc., thereby forming a negative electrode active material layer.
[0395] <Formation of each layer (film formation)>
[0396] The coating method of the inorganic solid electrolyte composition is not particularly limited and can be appropriately selected. For example, coating (preferably wet coating), spraying, spin coating, dip coating, slit coating, stripe coating, and rod coating can be cited. The coating temperature is not particularly limited, and is preferably a temperature at which at least the compound (A) does not volatilize. For example, a temperature range of room temperature (e.g., 15 to 30° C.) can be cited without heating.
[0397] The applied inorganic solid electrolyte composition is dried (heated). In the drying process, the dispersion medium (D) is usually removed (volatilized) without removing (volatilizing) the compound (A) in the applied inorganic solid electrolyte composition. The heating process can be performed after the inorganic solid electrolyte composition is applied separately or after multi-layer coating.
[0398] As for the drying conditions, as long as the dispersion medium (D) can be removed without removing the compound (A), it is not particularly limited, and can be appropriately selected by considering the boiling point and content of the compound (A) and the dispersion medium (D), the adsorption of the compound (A) and the polymer binder (B) and the solid particles. For example, as the drying temperature, it is preferably above 30°C, more preferably above 60°C, and more preferably above 80°C. The upper limit is preferably below 200°C, more preferably below 150°C, and more preferably below 120°C. By heating within this temperature range, the dispersion medium (D) can be removed without removing the compound (A), and it can be made into a solid state (coating a dry layer). Moreover, it is preferred that the temperature will not be too high and the components of the all-solid-state secondary battery will not be damaged. Thus, in the all-solid-state secondary battery, excellent comprehensive performance is shown, and good adhesion and good ionic conductivity can be obtained.
[0399] Preferably, after coating the inorganic solid electrolyte composition, after stacking the structural layers, or after making the all-solid-state secondary battery, each layer or the all-solid-state secondary battery is pressurized. In addition, it is also preferred to pressurize in a state where each layer is stacked. As a pressurization method, a hydraulic cylinder punching machine and the like can be cited. The pressurization pressure is not particularly limited, and is generally preferably in the range of 5 to 1500 MPa.
[0400] Furthermore, for the coated inorganic solid electrolyte composition, it is possible to heat while pressurizing. The heating temperature is not particularly limited, and is usually in the range of 30 to 300°C, but is set to a temperature at which the compound (A) is not removed, taking into account the boiling point of the compound (A) and the pressurization pressure. It is also possible to stamp at a temperature higher than the glass transition temperature of the inorganic solid electrolyte. In addition, it is also possible to stamp at a temperature higher than the glass transition temperature of the polymer contained in the polymer binder. Among them, it is usually a temperature that does not exceed the melting point of the polymer.
[0401] The pressurization may be performed in a state where the coating solvent or dispersion medium is dried in advance, or may be performed in a state where the solvent or dispersion medium remains.
[0402] In addition, the compositions may be applied simultaneously, or applied, dried, and pressed simultaneously and / or sequentially. The compositions may be applied to different substrates and then laminated by transfer.
[0403] The atmosphere in the film forming method (coating, drying, pressurization (under heating)) is not particularly limited and can be any atmosphere such as atmospheric pressure, dry air (dew point below -20°C), inert gas (for example, argon, helium, nitrogen), etc.
[0404] Regarding the stamping time, high pressure can be applied for a short time (for example, within a few hours), or moderate pressure can be applied for a long time (more than 1 day). In addition to the sheet for all-solid-state secondary batteries, for example, in the case of all-solid-state secondary batteries, in order to continuously apply moderate pressure, the restraints of the all-solid-state secondary batteries (screw tightening pressure, etc.) can also be used. The stamping pressure on the pressure-bearing part such as the surface of the sheet can be uniform or different pressures. The stamping pressure can be changed according to the area or film thickness of the pressure-bearing part. In addition, the same part can be changed to different pressures in stages. The stamping surface can be smooth or rough.
[0405] <Initialization>
[0406] The all-solid-state secondary battery manufactured as described above is preferably initialized after manufacturing or before use. The initialization is not particularly limited, and can be performed, for example, by performing the first charge and discharge under an increased pressing pressure and then releasing the pressure until the normal operating pressure of the all-solid-state secondary battery is reached.
[0407] [Applications of all-solid-state secondary batteries]
[0408] The all-solid-state secondary battery of the present invention can be applied to various purposes. There is no particular restriction on the application mode. For example, when it is mounted on an electronic device, a notebook computer, a pen input computer, a mobile computer, an e-book reader, a mobile phone, a wireless telephone handset, a pager, a handheld terminal, a portable fax machine, a portable copier, a portable printer, a stereo headset, a camcorder, a liquid crystal television, a portable vacuum cleaner, a portable CD, a small disk, an electric shaver, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, etc. can be cited. As other civilian products, automobiles (electric cars, etc.), electric cars, motors, lighting fixtures, toys, game consoles, load regulators, clocks, flashlights, cameras, medical equipment (pacemakers, hearing aids, shoulder massagers, etc.) can be cited. In addition, it can be used as various military products and aviation products. And, it can also be combined with solar cells.
[0409] Example
[0410] The present invention is further described in detail below based on the examples, but the present invention is not limited thereto and should be interpreted. In the following examples, unless otherwise specified, the "parts", "%" and "ppm" representing the composition are based on mass. In the present invention, "room temperature" means 25°C.
[0411] 1. Polymer Synthesis
[0412] Polymers M-1 to M-8 represented by the following chemical formulas were synthesized as follows to prepare binder solutions or dispersions containing the respective polymers.
[0413] [Synthesis Example M-1] Synthesis of polymer M-1 and preparation of adhesive solution M-1
[0414] In the following Synthesis Example M-2, the compounds of each constituent component are derived in such a manner that the polymer M-1 has the composition (type and content of constituent components) shown in the following chemical formula, and the polymerization concentration and the amount of polymerization initiator are appropriately adjusted so that it becomes the mass average molecular weight shown in Table 2. In addition, the polymer M-1 ((meth) acrylic polymer) is synthesized in the same manner as in Synthesis Example M-2, thereby obtaining a xylene solution M-1 (concentration 30 mass %) of the polymer M-1.
[0415] [Synthesis Example M-2] Synthesis of polymer M-2 and preparation of adhesive solution M-2
[0416] In a 200 mL measuring cylinder, 21.6 g of methyl methacrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation), 46.1 g of dodecyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), 3.6 g of 2-hydroxyethyl acrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation), 0.8 g of monomethyl maleate (manufactured by Tokyo Chemical Industry Co., Ltd.) and 0.05 g of polymerization initiator V-601 (product name, manufactured by FUJIFILM Wako Pure Chemical Corporation) were added and dissolved in 27.0 g of butyl butyrate to prepare a monomer solution.
[0417] In a 500mL three-necked flask, 43.0g of butyl butyrate was added and heated to 80°C, and a solution obtained by dissolving 0.03g of polymerization initiator V-601 (product name) in 2.0g of butyl butyrate under a nitrogen atmosphere was added to the above flask and stirred at 80°C. The above monomer solution was added dropwise thereto over 2 hours. After the addition was completed, it was stirred at 80°C for 2 hours, then heated to 90°C and stirred for 2 hours. The obtained polymer solution was poured into 960g of methanol, stirred for 10 minutes, and then allowed to stand for 10 minutes. The precipitate obtained after removing the supernatant was dissolved in 120g of xylene, and solvent distillation was performed at 30hPa and 60°C. 80g of xylene was further added, and the solvent distillation process under the above conditions was repeated until methanol was not contained (below the detection limit in the determination based on gas chromatography).
[0418] In this manner, a polymer M-2 (a (meth)acrylic acid-based polymer) was synthesized, and a xylene solution M-2 (concentration: 30% by mass) of the polymer M-2 was obtained.
[0419] Then, butyl butyrate was used as a solvent for dissolving the precipitate instead of xylene, thereby obtaining a butyl butyrate solution (concentration: 30% by mass) of the polymer M-2.
[0420] [Synthesis Example M-3] Synthesis of polymer M-3 and preparation of adhesive solution M-3
[0421] In the above-mentioned Synthesis Example M-2, the compounds of each constituent component were derived in such a manner that the polymer M-3 had the composition (type and content of constituent components) shown in the following chemical formula, and the polymerization concentration and the amount of polymerization initiator were appropriately adjusted so that it became the mass average molecular weight shown in Table 2. In addition, the polymer M-3 ((meth) acrylic polymer) was synthesized in the same manner as in Synthesis Example M-2, thereby obtaining a xylene solution M-3 (concentration 30 mass %) of the polymer M-3.
[0422] [Synthesis Example M-4] Synthesis of polymer M-4 and preparation of adhesive solution M-4
[0423] In the autoclave, 150 parts by mass of toluene, 30 parts by mass of styrene and 70 parts by mass of 1,3-butadiene were added, and 1 part by mass of polymerization initiator V-601 (manufactured by FUJIFILM Wako Pure Chemical Corporation) was added, and the temperature was raised to 80°C and stirred for 3 hours. Thereafter, the temperature was raised to 90°C for reaction until the conversion rate reached 100%. The obtained solution was precipitated again in methanol, and 3 parts by mass of 2,6-di-tert-butyl-p-cresol and 2.2 parts by mass of maleic anhydride were added to 100 parts by mass of the polymer obtained by drying the obtained solid, and the reaction was carried out at 180°C for 5 hours. The obtained solution was precipitated again in acetonitrile, and the obtained solid was dried at 80°C to obtain a polymer (dried solid). The mass average molecular weight of the polymer is 90,000. Then, 50 parts by mass of the polymer (dry solid) obtained above was dissolved in 50 parts by mass of cyclohexane and 150 parts by mass of THF (tetrahydrofuran), and the solution was heated to 70° C., and 3 parts by mass of n-butyl lithium, 3 parts by mass of 2,6-di-tert-butyl-p-cresol, 1 part by mass of bis(cyclopentadienyl)titanium dichloride and 2 parts by mass of diethylaluminum chloride were added, and the mixture was stirred at a hydrogen pressure of 10 kg / cm 2 After the reaction was allowed to proceed for 1 hour, the solvent was distilled off and the mixture was dried to obtain a hydrocarbon polymer precursor A (mass average molecular weight: 90,000).
[0424] On the other hand, 100 parts by mass of xylene (manufactured by FUJIFILM Wako Pure Chemical Corporation) was added to a 2L three-necked flask with a reflux cooling tube and a gas introduction plug, and nitrogen was introduced at a flow rate of 100 mL / min for 10 minutes, and then the temperature was raised to 80°C. A mixed solution of 12.2 parts by mass of 2-aminoethanethiol hydrochloride (manufactured by Tokyo Chemical Industry Co., Ltd.) and 100 parts by mass of ethanol (manufactured by FUJIFILM Wako Pure Chemical Corporation) and a mixed solution of 400 parts by mass of lauryl acrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation), 100 parts by mass of hydroxyethyl acrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation), 170 parts by mass of xylene (manufactured by FUJIFILM Wako Pure Chemical Corporation) and 10 parts by mass of azobisbutyronitrile (manufactured by FUJIFILM Wako Pure Chemical Corporation) were separately added dropwise to the three-necked flask over 2 hours. After the addition, the mixture was further stirred at 80°C for 2 hours. Thereafter, the mixture was added dropwise to methanol to obtain a macromonomer having a terminal amino group (hydrochloride) as a precipitate. The mass average molecular weight of the macromonomer was 3,000.
[0425] Next, 450 parts by mass of xylene (manufactured by FUJIFILM Wako Pure Chemical Corporation) and 50 parts by mass of the above hydrocarbon polymer precursor A were placed in a 1L three-necked flask with a reflux cooling tube and a gas introduction plug, and dissolved. Thereafter, 68 parts by mass of the aforementioned terminal amino macromonomer and 1.6 parts by mass of 1,8-diazabicycloundecene (DBU, manufactured by FUJIFILM Wako Pure Chemical Corporation) were added, and the temperature was raised to 130°C, and stirring was continued for 10 hours. Thereafter, 1 aqueous hydrochloric acid solution of a specified concentration was added and the organic layer was separated and removed, and the organic layer was added dropwise to acetone to obtain polymer M-4 as a precipitate. After drying under reduced pressure at 60°C for 5 hours, it was dissolved in butyl butyrate. In this way, polymer M-4 (hydrocarbon polymer, mass average molecular weight 130,000) was synthesized, and a butyl butyrate solution (concentration 15% by mass) of polymer M-4 was obtained.
[0426] Then, as a solvent for redissolving the polymer M-4 obtained as a precipitate after drying, xylene was used instead of butyl butyrate to obtain a xylene solution of the polymer M-4 (concentration: 15% by mass).
[0427] [Synthesis Example M-5] Synthesis of polymer M-5 and preparation of adhesive solution M-5
[0428] In an autoclave, 200 parts by mass of ion exchange water, 80 parts by mass of vinylidene fluoride, 98 parts by mass of hexafluoropropylene, 20 parts by mass of 2-hydroxyethyl acrylate and 2 parts by mass of acrylic acid were added, and 1.5 parts by mass of diisopropyl peroxydicarbonate were further added thereto, and stirred at 30°C for 24 hours. After the polymerization was completed, the precipitate was filtered and dried at 100°C for 10 hours to obtain a polymer (fluoropolymer) M-5. The obtained polymer is a random copolymer having a mass average molecular weight of 230,000. The obtained polymer M-5 was dissolved in butyl butyrate to obtain a butyl butyrate solution (concentration 15% by mass) of the polymer M-5.
[0429] [Synthesis Example M-6] Synthesis of polymer M-6 and preparation of adhesive dispersion M-6
[0430] Toluene (269.0 g) was placed in a 1-liter three-necked flask equipped with a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, and the temperature was raised to 80°C under a nitrogen flow. Next, a monomer solution consisting of 150.2 g of methyl methacrylate, 381.6 g of lauryl methacrylate, 5.3 g of V-601 (manufactured by FUJIFILM Wako Pure Chemical Corporation), and 4.7 g of mercaptopropionic acid was dripped into the three-necked flask at a constant rate in 2 hours. After the dropwise addition of the monomer solution was completed, the mixture was stirred for 2 hours, then heated to 95°C, and further stirred for 2 hours. Next, 0.3 g of p-methoxyphenol, 31.8 g of glycidyl methacrylate, and 6.4 g of tetrabutylammonium bromide were added to the obtained reaction mixture, the temperature was raised to 120°C, and the mixture was stirred for 3 hours. Thereafter, the reaction solution was cooled to room temperature, and the reaction solution was injected into 2 L of methanol being stirred, and allowed to stand for a while. The solid obtained by decanting the supernatant was dissolved in 1200 g of xylene, and the solvent was distilled off under reduced pressure until the solid content was 40%, thereby obtaining a macromonomer solution. The mass average molecular weight of the macromonomer was 20,000.
[0431] Next, 167 g of butyl butyrate and 112.5 g of macromolecular monomer solution (40.0% solid content) were added to a 1-liter three-necked flask equipped with a stirrer, a thermometer, a reflux cooling tube and a nitrogen inlet tube, and the temperature was raised to 80°C under a nitrogen stream. Next, a monomer solution consisting of 105.0 g of succinic acid mono(2-acryloyloxyethyl), 115.5 g of xylene and 1.5 g of V-601 was dripped into the three-necked flask at a constant speed in a manner that the addition was completed in 2 hours. After the addition of the monomer solution was completed, it was stirred for 2 hours, then heated to 90°C and further stirred for 2 hours. The obtained reaction mixture was filtered through a sieve with a mesh of 50 μm. In this way, a butyl butyrate dispersion M-6 (concentration 30% by mass) of polymer M-6 ((meth) acrylic polymer) was obtained. The average particle size of the adhesive composed of polymer M-6 is 250 nm.
[0432] [Synthesis Example M-7] Synthesis of polymer M-7 and preparation of adhesive solution M-7
[0433] In the above-mentioned Synthesis Example M-2, the compounds of each constituent component are derived in a manner so that the polymer M-7 has the composition (type and content of constituent components) shown in the following chemical formula, and the polymerization concentration and the amount of polymerization initiator are appropriately adjusted so that it becomes the mass average molecular weight shown in Table 2. In addition, the polymer M-7 ((meth) acrylic polymer) is synthesized in the same manner as in Synthesis Example M-2, thereby obtaining a xylene solution M-7 (concentration 30 mass %) of the polymer M-7.
[0434] [Synthesis Example M-8] Synthesis of polymer M-8 and preparation of adhesive solution M-8
[0435] In the above-mentioned Synthesis Example M-2, the compounds of each constituent component were derived in such a manner that the polymer M-8 had the composition (type and content of constituent components) shown in the following chemical formula, and the polymerization concentration and the amount of polymerization initiator were appropriately adjusted so that it became the mass average molecular weight shown in Table 2. In addition, the polymer M-8 ((meth) acrylic polymer) was synthesized in the same manner as in Synthesis Example M-2, thereby obtaining a xylene solution M-8 (concentration 30% by mass) of the polymer M-8.
[0436] The synthesized polymers are shown below. The numerical value on the lower right of each component indicates the content (mass %). In the following polymers, Me represents a methyl group, MMA represents methyl methacrylate, LMA represents lauryl methacrylate, and "wt %" represents mass %.
[0437] [Chemical formula 2]
[0438]
[0439] For each polymer synthesized, the type and mass average molecular weight of the polymer are shown in the "Polymer Binder (B)" column of Table 2 described later. The mass average molecular weight was measured by the above method. In addition, in each polymer, the terminal group used to determine the difference between the residue of compound (A) and the terminal group is shown in the "Terminal Group" column of Table 2.
[0440] 2. Preparation of compound (A)
[0441] As compounds A-1 to A-11 represented by the following chemical formulas, commercially available products were used.
[0442] Compound A-1: manufactured by FUJIFILM Wako Pure Chemical Corporation
[0443] Compound A-2: manufactured by FUJIFILM Wako Pure Chemical Corporation
[0444] Compound A-3: manufactured by FUJIFILM Wako Pure Chemical Corporation
[0445] Compound A-4: manufactured by FUJIFILM Wako Pure Chemical Corporation
[0446] Compound A-5: manufactured by FUJIFILM Wako Pure Chemical Corporation
[0447] Compound A-6: manufactured by FUJIFILM Wako Pure Chemical Corporation
[0448] Compound A-7: X-22-176DX, manufactured by Shin-Etsu Chemical Co., Ltd.
[0449] Compound A-8: manufactured by FUJIFILM Wako Pure Chemical Corporation
[0450] Compound A-9: manufactured by FUJIFILM Wako Pure Chemical Corporation
[0451] Compound A-10: manufactured by FUJIFILM Wako Pure Chemical Corporation
[0452] Compound A-11: manufactured by FUJIFILM Wako Pure Chemical Corporation
[0453] The compounds are shown below. In compound A-7, R S1 , R S2 and R S3 represents a substituent.
[0454] The type of functional group (a) and the (number average) molecular weight of each compound are shown in Table 2. The number average molecular weight of compound A-7 was measured by the above method. The residue in each compound is shown in the "Residue" column of Table 2.
[0455] [Chemical formula 3]
[0456]
[0457] 3. Synthesis of sulfide-based inorganic solid electrolytes
[0458] [Synthesis Example A]
[0459] With reference to the non-patent literature of T.Ohtomo, A.Hayashi, M.Tatsumisago, Y.Tsuchida, S.Hama, K.Kawamoto, Journal of Power Sources, 233, (2013), pp231-235 and A.Hayashi, S.Hama, H.Morimoto, M.Tatsumisago, T.Minami, Chem.Lett., (2001), pp872-873, a sulfide-based inorganic solid electrolyte was synthesized.
[0460] Specifically, 2.42 g of lithium sulfide (Li2S, manufactured by Aldrich, purity>99.98%) and 3.90 g of phosphorus pentasulfide (P2S5, manufactured by Aldrich, purity>99%) were weighed in a glove box under an argon atmosphere (dew point -70°C), put into an agate mortar, and mixed for 5 minutes using an agate pestle. The mixing ratio of Li2S and P2S5 was set to Li2S:P2S5=75:25 in terms of molar ratio.
[0461] Next, 66 g of zirconia beads with a diameter of 5 mm were added to a 45 mL container made of zirconium oxide (manufactured by Fritsch Co., Ltd.), and the mixture of the above-mentioned lithium sulfide and phosphorus pentasulfide was added in full, and the container was completely sealed under an argon atmosphere. The container was set in a planetary ball mill P-7 (product name, manufactured by Fritsch Co., Ltd.), and mechanical grinding was performed for 20 hours at a temperature of 25°C and a rotation speed of 510 rpm, thereby obtaining 6.20 g of a yellow powder sulfide inorganic solid electrolyte (Li-PS glass, hereinafter sometimes marked as LPS). The particle size of the Li-PS glass is 15 μm.
[0462] [Example 1]
[0463] Each composition shown in Table 1-1 to Table 1-4 (collectively referred to as Table 1) was prepared as follows.
[0464] <Preparation of Inorganic Solid Electrolyte Composition>
[0465] Into a container for an auto-rotating revolution mixer (ARE-310, manufactured by THINKY CORPORATION), 2.8 g of the inorganic solid electrolyte LPS synthesized in Synthesis Example A, 0.08 g of a binder solution or a binder dispersion (solid content mass), the content of the compound (A) shown in Table 1 relative to 100% by mass of the solid content is the content shown in the "Content*** (ppm)" column of Table 1, and the dispersion medium (D) described in Table 1, so that the content of the dispersion medium (D) in the composition becomes 48% by mass, and then the container is set in an auto-rotating revolution mixer ARE-310 (product name). Mixing was carried out at 25° C. and a rotation speed of 2000 rpm for 5 minutes to prepare inorganic solid electrolyte-containing compositions (slurries) S-1 to S-21 and Kc1 to Kc3, respectively.
[0466] The polymer M-2 solution and the polymer M-4 solution were prepared using the same solvent as the dispersion medium (D). The same was true for the positive electrode composition and the negative electrode composition.
[0467] <Preparation of positive electrode composition>
[0468] 2.8 g of the inorganic solid electrolyte LPS synthesized in Synthesis Example A and the dispersion medium (D) shown in Table 1 were added to a container for a self-rotating revolution mixer (ARE-310, manufactured by THINKY CORPORATION) so that the content of the dispersion medium (D) in the positive electrode composition became 30% by mass. Thereafter, the container was placed in the self-rotating revolution mixer ARE-310 (product name) and mixed for 2 minutes at a temperature of 25°C and a rotation speed of 2000 rpm. Thereafter, LiNi as a positive electrode active material was added to the container in a ratio to become the content shown in Table 1 (for compound (A), the content is the content shown in the "Content*** (ppm)" column of Table 1). 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NMC, manufactured by Aldrich, CO.LTD.), acetylene black (AB) as a conductive aid, 0.133 g (solid content mass) of the binder solution or polymer binder (B) shown in Table 1, and the compound (A) shown in Table 1 were set in an auto-revolution mixer ARE-310 (product name) and mixed for 2 minutes at 25°C and a rotation speed of 2000 rpm to prepare positive electrode compositions (slurries) PK-1 to PK-21 and PKc21 to PKc23, respectively.
[0469] <Preparation of negative electrode composition>
[0470] Into a container for an auto-rotating revolution mixer (ARE-310), 2.8 g of the inorganic solid electrolyte LPS synthesized in Synthesis Example A, 0.062 g (solid content mass) of the binder solution or polymer binder (B) shown in Table 1 below, the content of the compound (A) shown in Table 1 relative to 100% by mass of the solid content was the content shown in the "Content*** (ppm)" column of Table 1, and the dispersion medium (D) shown in Table 1 were placed so that the content of the dispersion medium (D) in the negative electrode composition became 48% by mass. Thereafter, the container was placed in an auto-rotating revolution mixer ARE-310 (product name) manufactured by THINKY CORPORATION, and mixing was performed for 2 minutes at 25° C. and a rotation speed of 2000 rpm. Subsequently, 3.11 g of silicon (Si, manufactured by Aldrich) as the negative electrode active material shown in the following Table 1 and 0.25 g of carbon nanotubes (VGCF) as a conductive aid were added, and the mixture was similarly placed in an ARE-310 (product name) rotary mixer and mixed for 2 minutes at 25°C and a rotation speed of 2000 rpm, thereby preparing negative electrode compositions (slurries) NK-1 to NK-21 and NKc21 to NKc23, respectively.
[0471] In Table 1, the composition content is the content (mass %) relative to the total mass of the composition, and the solid content is the content (mass %) relative to 100% by mass of the solid content of the composition, and the units are omitted in the table. In addition, as the content of the compound (A) in each composition, the content relative to the inorganic solid electrolyte (SE), the content relative to the polymer binder (B), and the content relative to 100% by mass of the solid content are shown in the "Content * (ppm)" column, the "Content ** (mass %)" column, and the "Content *** (ppm)" column of Table 1, respectively. In addition, in the "State" column of Table 1, the state of the polymer binder (B) and the compound (A) in each composition (dissolved (marked as "dissolved" in Table 1) or insoluble and dispersed in particles (marked as "particles" in Table 1)) is shown as the result evaluated by the above-mentioned solubility measurement.
[0472]
[0473]
[0474]
[0475]
[0476] <Abbreviations in Table 1>
[0477] LPS: LPS synthesized in Synthesis Example A
[0478] NMC:LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2
[0479] Si: Silicon (APS 1-5 μm, manufactured by Alfa Aesar)
[0480] AB: Acetylene Black
[0481] VGCF: Carbon Nanotube
[0482] The combinations of polymer binders (B) and compounds (A) in each of the prepared compositions are summarized in Table 2, and the types of polymer binders (B), the terminal groups and mass average molecular weights used to determine the differences and similarities with the residues of compound (A), and the types, residues, and (number average) molecular weights of the functional groups (a) of compound (A) are shown in Table 2. Compound A-9 has no residues, so the molecular formula is shown in the "Residue" column. In addition, in Table 2, "Composition No." marks the No. of the extracted inorganic solid electrolyte composition.
[0483]
[0484] <Abbreviations in Table 2>
[0485] SEBS: Styrene-ethylene-butylene-styrene block copolymer (hydrocarbon polymer)
[0486] PVDF-HFP: Copolymer of polyvinylidene fluoride and hexafluoropropylene (fluoropolymer)
[0487] Next, a sheet for an all-solid-state secondary battery was produced in the following manner.
[0488] <Manufacturing of solid electrolyte sheets for all-solid-state secondary batteries>
[0489] Using a Baker-type applicator (product name: SA-201, manufactured by TESTER SANGYO CO,.LTD.), each inorganic solid electrolyte composition shown in the "Solid Electrolyte Composition No." column of Table 3-1 or Table 3-4 obtained above was applied to an aluminum foil (substrate) with a thickness of 20 μm, and heated at 80°C for 2 hours to dry the inorganic solid electrolyte composition (removing compound (A) but not removing the dispersion medium (D)). Thereafter, using a hot press, the dried inorganic solid electrolyte composition was heated and pressurized at a temperature of 120°C and a pressure of 10 MPa for 10 seconds to produce solid electrolyte sheets for all-solid-state secondary batteries (marked as solid electrolyte sheets in Tables 3-1 and 3-4.) 101 to 121 and c11 to c13, respectively. The film thickness of the solid electrolyte layer is 50 μm.
[0490] <Manufacturing of positive electrode sheets for all-solid-state secondary batteries>
[0491] Using a Baker-type coater (product name: SA-201), each positive electrode composition shown in the "Electrode Composition No." column of Table 3-2 or Table 3-4 obtained above was applied to an aluminum foil (substrate) with a thickness of 20 μm, heated at 80°C for 1 hour, and then heated at 100°C for 1 hour, and the positive electrode composition was dried (the dispersion medium (D) was removed without removing the compound (A)). Thereafter, a hot press was used to pressurize the dried positive electrode composition at 25°C (10 MPa, 1 minute), and positive electrode sheets for all-solid-state secondary batteries (marked as positive electrode sheets in Tables 3-2 and 3-4) 201~221 and c21~c23 having a positive electrode active material layer with a film thickness of 100 μm were prepared.
[0492] <Manufacturing of negative electrode sheets for all-solid-state secondary batteries>
[0493] Using a Baker-type coater (product name: SA-201), each negative electrode composition shown in the "Electrode Composition No." column of Table 3-3 or Table 3-4 obtained above was applied to a copper foil (substrate) with a thickness of 20 μm, heated at 80°C for 1 hour, and then heated at 100°C for 1 hour, and the negative electrode composition was dried (the dispersion medium (D) was removed without removing the compound (A)). Thereafter, a hot press was used to pressurize the dried negative electrode composition at 25°C (10 MPa, 1 minute), and negative electrode sheets for all-solid-state secondary batteries (marked as negative electrode sheets in Tables 3-3 and 3-4) 301~321 and c31~c33 having a negative electrode active material layer with a film thickness of 70 μm were produced.
[0494] <Evaluation 1: Dispersion stability test (redispersibility)>
[0495] For each composition prepared in the above manner, LPS, polymer binder (B), compound (A), dispersion medium (D), active material (AC) and conductive auxiliary agent were mixed in the same ratio as the ratio of each content shown in Table 1 under the same conditions as the preparation of each composition, thereby preparing a composition (slurry) for dispersibility evaluation. For each prepared composition, a grinder (manufactured by Asahi Soken Co., Ltd.) was used to confirm the presence or absence of agglomerates of solid particles. The size of the agglomerates at this time was set to X (μm) as an index of initial dispersibility.
[0496] On the other hand, each of the prepared compositions was placed at 25°C for 24 hours and then mixed again at 25°C using a planetary ball mill P-7 (product name). The rotation speed and time during remixing were set to the same conditions as the preparation conditions of each composition. For the remixed composition, the above-mentioned grinder was used to confirm the presence or absence of agglomerates of solid particles. The size of the agglomerates at this time was set to Y (μm) as an indicator of redispersibility after storage.
[0497] The size of the aggregates was determined as the point at which the coating material on the grinder showed obvious spots (see JIS K-5600-2-56.6).
[0498] The ease of generation of aggregates (aggregation or precipitation) is evaluated as the dispersion stability of the composition by which of the following evaluation criteria the aggregate sizes X and Y are included. In this test, the smaller the size X of the aggregate, the better the initial dispersibility, and the smaller the size Y, the better the dispersion stability.
[0499] In this test, the size Y of the aggregate was evaluated as being at least D, and the size X of the aggregate was also included in the evaluation when the size Y was 8 μm or less (evaluation standard: C). The results are shown in Tables 3-1 to 3-4 (collectively referred to as Table 3).
[0500] -Evaluation Criteria-
[0501] A: Y≤5μm and X≤5μm
[0502] B: 5μm<Y≤8μm and 5μm<X≤8μm
[0503] C: 5μm<Y≤8μm and 8μm<X≤12μm
[0504] D: 8μm<Y≤10μm
[0505] E: 10μm<Y≤20μm
[0506] F: 20μm<Y
[0507] <Evaluation 2: Operation test>
[0508] In the same manner as each of the prepared compositions, except for the dispersion medium, the same mixing ratio was set, and the amount of the dispersion medium was reduced to prepare a slurry with a solid content concentration of 75% by mass. A 2mL poly dropper (manufactured by Atect Corporation) was vertically arranged so that the tip 10 mm entered below the slurry interface, and the slurry was sucked for 10 seconds at 25°C, and the mass W of the poly dropper containing the sucked slurry was measured. When the tare weight (self-weight) of the poly dropper is set to W0, the slurry mass W-W0 is judged to be unable to be sucked with a dropper when it is less than 0.1g. In the case where the slurry cannot be sucked with a dropper, the upper limit solid content concentration that can be sucked with a dropper is grasped while gradually adding the dispersion medium. Depending on which of the following evaluation criteria the obtained upper limit solid content concentration is included, the operability of each composition (whether it has a moderate viscosity to form a flat and well-surfaced structural layer) was evaluated. Regarding the solid content concentration, 0.30g of the prepared slurry was placed on an aluminum cup and heated at 120°C for 2 hours to distill the dispersion medium for calculation.
[0509] In this test, the higher the upper limit solid content concentration, the better the workability, and the evaluation standard "D" or higher was considered a pass level. The results are shown in Table 3.
[0510] -Evaluation Criteria-
[0511] A: Upper limit solid content concentration ≥ 70%
[0512] B: 70%>upper limit solid content concentration≥60%
[0513] C: 60%>Upper limit solid content concentration ≥ 50%
[0514] D: 50%>upper limit solid content concentration≥40%
[0515] E: 40%>Upper limit solid content concentration ≥ 30%
[0516] F: 30% > upper limit solid content concentration
[0517] <Evaluation 3: Adhesion test>
[0518] The adhesion of solid particles in the solid electrolyte layer of each obtained sheet and the adhesion of the solid electrolyte layer to the substrate, and the adhesion of solid particles in the active material layer of each electrode sheet and the adhesion of the active material layer to the substrate were evaluated.
[0519] Each sheet produced was cut into a rectangle of 3cm wide and 14cm long. Using a cylindrical mandrel testing machine (product code 056, mandrel diameter 10mm, manufactured by Allgood), one end of the cut sheet test piece in the length direction was fixed on the above-mentioned testing machine, and the cylindrical mandrel was arranged in a manner that abutted the central part of the sheet test piece, and the other end of the long side direction of the sheet test piece was stretched along the long side direction with a force of 5N, while being bent 180° along the circumference of the mandrel (with the mandrel as the axis). In addition, for the sheet test piece, the solid electrolyte layer or the active material layer was arranged on the side opposite to the mandrel in a manner parallel to the axis of the mandrel in the width direction (the substrate was arranged on the mandrel side). The test was carried out in a manner that the diameter of the mandrel was gradually reduced from 32mm.
[0520] The evaluation was conducted as follows: in the state of being wound on the mandrel and in the state of being unwound and restored to a sheet, the minimum diameter at which no defects (cracks, ruptures, notches, etc.) caused by the collapse of the bonding of solid particles in the solid electrolyte layer or the active material layer, or even the peeling between the solid electrolyte layer and the substrate or the peeling between the active material layer and the substrate were confirmed, and which of the following evaluation criteria the minimum diameter corresponds to was measured. The results are shown in Table 3.
[0521] In this test, the smaller the minimum diameter is, the stronger the binding force of the solid particles constituting the solid electrolyte layer or the active material layer is and the stronger the adhesion to the substrate is. Evaluation criteria "C" or higher are considered acceptable levels.
[0522] -Evaluation Criteria-
[0523] A: Minimum diameter <5mm
[0524] B: 5mm≤minimum diameter<6mm
[0525] C: 6mm≤minimum diameter<8mm
[0526] D: 8mm≤minimum diameter<10mm
[0527] E: 10mm≤minimum diameter
[0528] <Evaluation 4: Determination of the content of compound (A)>
[0529] The content of the compound (A) contained in the solid electrolyte layer or active material layer of each sheet obtained is measured as follows, and the content in the solid electrolyte layer or active material layer is calculated. And, based on the obtained content, the content relative to the inorganic solid electrolyte (SE) and the content of the compound (A) relative to the polymer binder (B) are calculated. The obtained results are roughly consistent with the contents in the inorganic solid electrolyte composition recorded in the "Content *** (ppm)" column, "Content * (ppm)" column, and "Content ** (mass %)" column of Table 1.
[0530] (Method for measuring the content of compound (A) in solid electrolyte layer or active material layer)
[0531] The mass of the solid electrolyte layer or active material layer (10 to 100 mg) was accurately weighed, immersed in 4 mL of xylene, and vibrated for 1 hour using an ultrasonic cleaner. The content of compound (A) in the supernatant solution of the obtained eluate was quantified by gas chromatography.
[0532] [Table 3-1]
[0533]
[0534] [Table 3-2]
[0535]
[0536] [Table 3-3]
[0537]
[0538] [Table 3-4]
[0539]
[0540] <Manufacturing of all-solid-state secondary batteries>
[0541] First, a positive electrode sheet for an all-solid-state secondary battery having a solid electrolyte layer and a negative electrode sheet for an all-solid-state secondary battery having a solid electrolyte layer were prepared.
[0542] -Production of positive electrode sheet for all-solid-state secondary battery with solid electrolyte layer-
[0543] The solid electrolyte sheet shown in the "Solid Electrolyte Layer (Sheet No.)" column of Table 4-1 produced above was overlapped on the positive electrode active material layer of each all-solid-state secondary battery positive electrode sheet shown in the "Electrode Active Material Layer (Sheet No.)" column of Table 4-1 in such a manner that the solid electrolyte layer was in contact with the positive electrode active material layer, and after being pressurized and transferred (laminated) at 50 MPa at 25°C using a punch, pressurized at 600 MPa at 25°C, thereby producing all-solid-state secondary battery positive electrode sheets (positive electrode active material layer with a thickness of 50 μm) No. 201~221, c21~c23 respectively having a solid electrolyte layer with a film thickness of 25 μm.
[0544] -Production of negative electrode sheet for all-solid-state secondary battery with solid electrolyte layer-
[0545] The solid electrolyte sheet shown in the "Solid Electrolyte Layer (Sheet No.)" column of Table 4-2 produced above was overlapped on the negative electrode active material layer of each all-solid-state secondary battery negative electrode sheet shown in the "Electrode Active Material Layer (Sheet No.)" column of Table 4-2 in such a manner that the solid electrolyte layer was in contact with the negative electrode active material layer, and after being pressurized and transferred (laminated) at 50 MPa at 25°C using a punch, pressurized at 600 MPa at 25°C, thereby producing all-solid-state secondary battery negative electrode sheets (negative electrode active material layer with a thickness of 40 μm) 301~321, c31~c33 respectively having a solid electrolyte layer with a film thickness of 25 μm.
[0546] The following method was used to produce Figure 1 All-solid-state secondary battery No. 101 having the layer structure shown.
[0547] The all-solid-state secondary battery positive electrode sheet No. 201 with a solid electrolyte layer obtained above (the aluminum foil of the sheet containing the solid electrolyte has been peeled off) was cut into a disc shape with a diameter of 14.5 mm. Figure 2 As shown, place the assembly with spacers and washers (in Figure 2 Next, a lithium foil cut into a disk shape with a diameter of 15 mm was stacked on the solid electrolyte layer. After the stainless steel foil was further stacked on top, the 2032-type button battery shell 11 was riveted to produce a Figure 2 All-solid-state secondary battery 13 of No. 101 is shown.
[0548] The all-solid-state secondary battery manufactured in this way has Figure 1 The layer structure shown (corresponding to the laminated body 12 for the all-solid-state secondary battery) (wherein the lithium foil corresponds to the negative electrode active material layer 2 and the negative electrode collector 1).
[0549] In the manufacture of the above-mentioned all-solid-state secondary battery No. 101, the all-solid-state secondary battery positive electrode sheet with a solid electrolyte layer represented by No. shown in the "Electrode active material layer (sheet No.)" column of Table 4-1 was used instead of the all-solid-state secondary battery positive electrode sheet No. 201 with a solid electrolyte layer. Apart from this, all-solid-state secondary batteries No. 102 to 121 and c101 to c103 were respectively manufactured in the same manner as the all-solid-state secondary battery No. 101.
[0550] The following method was used to produce Figure 1 All-solid-state secondary battery No. 201 having the layer structure shown.
[0551] The anode sheet No. 301 for all-solid-state secondary battery with solid electrolyte obtained above (the aluminum foil of the sheet containing solid electrolyte has been peeled off) was cut into a disc shape with a diameter of 14.5 mm, as shown in FIG. Figure 2 As shown, place the assembly with spacers and washers (in Figure 2 A stainless steel 2032 type button battery shell 11 (not shown in the figure) is then placed on top of the solid electrolyte layer. A stainless steel foil (positive electrode collector) is further placed on top of it to form a laminate 12 for a solid-state secondary battery (laminate consisting of stainless steel foil-aluminum foil-positive electrode active material layer-solid electrolyte layer-negative electrode active material layer-copper foil). Thereafter, the 2032 type button battery shell 11 is riveted to produce a Figure 2 All-solid-state secondary battery No.201 shown.
[0552] A positive electrode sheet for an all-solid-state secondary battery used in the production of all-solid-state secondary battery No. 201 was prepared as follows.
[0553] - Preparation of positive electrode composition -
[0554] Into a 45 mL container made of zirconium oxide (manufactured by Fritsch Co., Ltd.), 180 zirconium oxide beads with a diameter of 5 mm were added, and 2.7 g of LPS synthesized in the above synthesis example A, 0.3 g of KYNAR FLEX 2500-20 (product name, PVDF-HFP: polyvinylidene fluoride hexafluoropropylene copolymer, manufactured by ARKEMA) and 22 g of butyl butyrate were added. The container was set in a planetary ball mill P-7 (product name) manufactured by Fritsch Co., Ltd. and stirred at 25°C at a speed of 300 rpm for 60 minutes. Thereafter, 7.0 g of LiNi was added as a positive electrode active material. 1 / 3 Co 1 / 3 Mn1 / 3 Similarly, a container of O2(NMC) was placed in a planetary ball mill P-7, and mixing was continued at 25°C and 100 rpm for 5 minutes to prepare a positive electrode composition.
[0555] -Manufacturing of positive electrode sheets for all-solid-state secondary batteries-
[0556] The positive electrode composition obtained in the above was applied to an aluminum foil (positive electrode collector) having a thickness of 20 μm using a Baker coater (product name: SA-201, manufactured by TESTER SANGYO CO,.LTD.), and heated at 100°C for 2 hours to dry the positive electrode composition (remove the dispersion medium). Thereafter, the dried positive electrode composition was pressed at 25°C (10 MPa, 1 minute) using a hot press, thereby producing a positive electrode sheet for an all-solid-state secondary battery having a positive electrode active material layer having a film thickness of 80 μm.
[0557] In the manufacture of the above-mentioned all-solid-state secondary battery No. 201, the all-solid-state secondary battery negative electrode sheet with a solid electrolyte layer represented by No. shown in the "Electrode active material layer (sheet No.)" column of Table 4-2 was used instead of the all-solid-state secondary battery negative electrode sheet No. 301 with a solid electrolyte layer. Apart from this, all-solid-state secondary batteries No. 202 to 221 and c201 to c203 were respectively manufactured in the same manner as the all-solid-state secondary battery No. 201.
[0558] <Evaluation 5: Measurement of electrical resistance>
[0559] The resistance was evaluated by measuring the ionic conductivity of each manufactured all-solid-state secondary battery. Specifically, for each all-solid-state secondary battery, the AC impedance with a voltage amplitude of 5mV and a frequency of 1MHz to 1Hz was measured in a constant temperature bath at 25°C using a 1255B FREQUENCY RESPONSE ANALYZER (product name, manufactured by SOLARTRON). Thus, the resistance in the layer thickness direction of the sample for ionic conductivity measurement was obtained, and the ionic conductivity was calculated according to the following formula (C1). The results are shown in Table 4-1 and Table 4-2 (collectively referred to as Table 4.).
[0560] Formula (C1): Ionic conductivity σ (mS / cm) =
[0561] 1000× sample thickness (cm) / [resistance (Ω)× sample area (cm 2 )]
[0562] In formula (C1), the sample layer thickness is the value obtained by measuring and subtracting the thickness of the current collector (total thickness of the solid electrolyte layer and the electrode active material layer) before placing the all-solid secondary battery laminate 12 in the 2032-type button battery case 11. The sample area is the area of a disc-shaped sheet with a diameter of 14.5 mm.
[0563] It is determined whether the obtained ion conductivity σ falls within the following evaluation criteria.
[0564] Regarding the ion conductivity σ in this test, the evaluation standard "D" or higher is a pass level. In addition, from the above formula (C1), it can be seen that a larger ion conductivity σ means a smaller resistance.
[0565] -Evaluation Criteria-
[0566] A: 0.30≤σ
[0567] B: 0.25≤σ<0.30
[0568] C: 0.20≤σ<0.25
[0569] D: 0.15≤σ<0.20
[0570] E: σ<0.15
[0571] <Evaluation 6: Cycle characteristics>
[0572] The discharge capacity retention rate of each manufactured all-solid-state secondary battery was measured using a charge and discharge evaluation device TOSCAT-3000 (product name, manufactured by Toyosystem Corporation).
[0573] Specifically, at 25°C, the current density was 0.1 mA / cm 2 Each all-solid-state secondary battery was charged until the battery voltage reached 4.3 V. Thereafter, the battery was charged at a current density of 0.1 mA / cm 2 Discharge was performed until the battery voltage reached 2.5 V. This charge and discharge once was regarded as one charge and discharge cycle, and three charge and discharge cycles were repeated under the same conditions to initialize. Thereafter, the above charge and discharge cycles were repeated, and the discharge capacity of each all-solid-state secondary battery was measured using a charge and discharge evaluation device: TOSCAT-3000 (product name) during each charge and discharge cycle.
[0574] When the discharge capacity (initial discharge capacity) of the first cycle of charge and discharge after initialization is set to 100%, the battery characteristics (cycle characteristics) are evaluated according to which of the following evaluation criteria the number of charge and discharge cycles when the discharge capacity retention rate (discharge capacity relative to the initial discharge capacity) reaches 80%. In this test, the higher the evaluation standard, the better the battery characteristics (cycle characteristics), and the initial battery characteristics can be maintained even if multiple charge and discharge are repeated (even if used for a long time). Regarding the cycle characteristics in this test, the evaluation standard "C" or above is a qualified level. The results are shown in Table 4.
[0575] In addition, the initial discharge capacities of all-solid-state secondary batteries Nos. 101 to 121 and 201 to 221 all represent values at which they fully function as all-solid-state secondary batteries.
[0576] -Evaluation Criteria-
[0577] A: More than 600 cycles
[0578] B: 450 cycles or more and less than 600 cycles
[0579] C: 300 cycles or more and less than 450 cycles
[0580] D: 150 cycles or more and less than 300 cycles
[0581] E: Less than 150 cycles
[0582] <Evaluation 7: Determination of content of compound (A)>
[0583] Using the solid electrolyte layer or active material layer peeled or scraped from the all-solid-state secondary battery, the content of the compound (A) contained in the solid electrolyte layer or active material layer in the all-solid-state secondary battery is determined in the same manner as in the above-mentioned <Evaluation 4>, and the content in the solid electrolyte layer or active material layer is calculated. And, based on the obtained content, the content relative to the inorganic solid electrolyte (SE) and the content of the compound (A) relative to the polymer binder (B) are calculated. The results obtained are roughly consistent with the contents of the inorganic solid electrolyte composition recorded in the "Content *** (ppm)" column, the "Content * (ppm)" column, and the "Content ** (mass %)" column of Table 1.
[0584] [Table 4-1]
[0585]
[0586] [Table 4-2]
[0587]
[0588] From the results shown in Tables 3 and 4, the following can be understood.
[0589] Compared with the inorganic solid electrolyte and the polymer binder, the dispersion characteristics (storage stability and operability) and adhesion of the inorganic solid electrolyte composition (electrode composition) of the comparative example not containing the compound (A) specified in the present invention are poor. As a result, it can be seen that the all-solid-state secondary battery of the comparative example having an inorganic solid electrolyte layer or an active material layer formed by the composition is poor in at least the cycle characteristics, and it is impossible to take into account both the suppression of resistance rise and the improvement of cycle characteristics.
[0590] In contrast, the inorganic solid electrolyte composition (electrode composition) containing the compound (A) specified in the present invention is used simultaneously for the inorganic solid electrolyte (SE) and the polymer binder (B) in the dispersion medium (D) and has excellent dispersion characteristics and can enhance the adhesion of solid particles. The all-solid-state secondary battery of the present invention having an inorganic solid electrolyte layer or an active material layer formed by these compositions shows high ion conductivity (low resistance) and can also achieve excellent cycle characteristics. In particular, it is known that each composition (S-1, S-6 to S-9 and S-13, S-14, S-16, S-17, S-20 and S-21 shown in the "Composition No." column in Table 2) of the terminal group (the "terminal group" column in Table 2) of the polymer composed of the polymer binder (B) bonded to the heteroatom linking group) is used simultaneously. It can be considered that the dispersion characteristics, resistance and cycle characteristics are taken into account at a high level.
[0591] The present invention has been described together with its embodiments, but unless otherwise specified, the present invention is not intended to be limited to any of the details described, and it is deemed to be widely interpreted without departing from the spirit and scope of the invention as set forth in the appended claims.
[0592] This application claims priority based on Japanese Patent Application No. 2022-158086 filed in Japan on September 30, 2022, the contents of which are incorporated herein by reference as a part of what is described in this specification.
[0593] Explanation of symbols
[0594] 1-negative electrode collector, 2-negative electrode active material layer, 3-solid electrolyte layer, 4-positive electrode active material layer, 5-positive electrode collector, 6-working part, 10-all-solid-state secondary battery, 11-2032 type button battery shell, 12-laminated body for all-solid-state secondary battery, 13-button-type all-solid-state secondary battery.
Claims
1. An inorganic solid electrolyte composition comprising: an inorganic solid electrolyte (SE) having ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, a polymer binder (B), a compound (A) and a dispersion medium (D), wherein the inorganic solid electrolyte composition satisfies the following conditions (1) to (4), Condition (1) The mass average molecular weight of the polymer constituting the polymer binder (B) is 2,000 or more, Condition (2) The compound (A) has at least one functional group selected from the following functional group group (a), Condition (3) The molecular weight of the compound (A) is less than 2,000, Condition (4): the compound (A) is dissolved in the dispersion medium (D), [Functional group (a)] Hydroxyl, amino, carboxyl, sulfonic acid, phosphoric acid, phosphonic acid, cyano, thiol, sulfinyl.
2. The inorganic solid electrolyte composition according to claim 1, wherein The content of the compound (A) is 10 ppm or more relative to 100% by mass of the solid content of the inorganic solid electrolyte composition and 2.0×10 3 Below ppm.
3. The inorganic solid electrolyte composition according to claim 1, wherein The polymer binder (B) is dissolved in the dispersion medium (D).
4. The inorganic solid electrolyte composition according to claim 1, wherein The molecular weight of the compound (A) is less than 600.
5. The inorganic solid electrolyte composition according to claim 1, wherein The compound (A) satisfies the following condition (5), Condition (5) The residue after removing the functional group from the compound (A) has the same chemical structure as the terminal group bonded to the heteroatom linking group of the polymer constituting the polymer binder (B).
6. The inorganic solid electrolyte composition according to claim 2, wherein: The polymer binder (B) is dissolved in the dispersion medium (D), The molecular weight of the compound (A) is less than 600, The compound (A) satisfies the following condition (5), Condition (5) The residue after removing the functional group from the compound (A) has the same chemical structure as the terminal group bonded to the heteroatom linking group of the polymer constituting the polymer binder (B).
7. The inorganic solid electrolyte composition according to claim 1, wherein The polymer binder (B) is a (meth)acrylic polymer.
8. The inorganic solid electrolyte-containing composition according to claim 1, comprising an active material (AC). 9 . A sheet for an all-solid-state secondary battery, comprising a layer formed from the inorganic solid electrolyte-containing composition according to claim 1 .
10. An all-solid-state secondary battery, comprising, in sequence, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer, wherein: At least one of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer is a layer formed of the inorganic solid electrolyte-containing composition according to any one of claims 1 to 8. 11 . A method for producing a sheet for an all-solid-state secondary battery, comprising forming a film of the inorganic solid electrolyte-containing composition according to claim 1 . 12 . A method for manufacturing an all-solid-state secondary battery, comprising manufacturing the all-solid-state secondary battery by the manufacturing method according to claim 11 .
Citation Information
Patent Citations
Latex agglutination reaction measuring instrument
JP1987022066A
Catalyst carrier and production thereof
JP1990006856A
Four-wheel steering device
JP1991045473A
Distortion compensator
JP1993090844A
Assignment decision support system
JP1994004516A